Biomass-derived ceramic packing coupled with an Fe–Mn modified graphite felt cathode for enhanced bioelectro-Fenton/biotrickling filtration of gas-phase styrene - Shu-Hui Liu; Yu-Sheng Yang; Chi-Wen Lin; Rabia Tasaduq Hussain (Biomass and Bioenergy, 2026)

MEK inhibitor cobimetinib increases calreticulin and induces immune modulation in TNBC - Ling-Ming Tseng; Ka-Yi Lau; Ji-Lin Chen; Pei-Yi Chu; Chun-Teng Huang; Wan-Lun Wang; Yuan-Ya Chang; Jiun-I Lai; Chi-Cheng Huang; Ming-Shen Dai; Chun-Yu Liu (Journal of Molecular Medicine, 2026)
Immunogenic cell death (ICD) can activate immune cells and potentiate the response to immunotherapy. The mitogen-activated protein kinase (MAPK) signaling pathway regulates the immune response and mediates T-cell receptor signaling. Activation of the MAPK signaling pathway decreases the levels of tumor-infiltrating lymphocytes in triple-negative breast cancer (TNBC) and is associated with worse survival. Here, we investigated the potential of the MEK inhibitor cobimetinib as an ICD inducer in TNBC. We demonstrated that cobimetinib elicited hallmarks of ICD, including elevated levels of damage-associated molecular patterns. Ectopic ERK expression attenuated cobimetinib-induced CRT. Cobimetinib also evoked caspase-8 activation with increased Bax and Bak expression, while caspase inhibitor suppressed cobimetinib-induced CRT expression and apoptosis. In immunocompetent (BALB/c) mice bearing 4T1 tumors, cobimetinib exhibited stronger tumor growth inhibition than in immunodeficient (nude) mice, suggesting an immune-dependent antitumor effect. Furthermore, cobimetinib treatment increased the proportions of naïve CD8 + T cells and effector CD4 + T cells and decreases the proportion of myeloid-derived suppressor cells in immunocompetent mice bearing 4T1 tumors. Notably, we observed differential immunomodulatory effects of cobimetinib in tumor-bearing mice compared to non–tumor-bearing immunocompetent mice. Our findings indicate that MEK inhibition is associated with ICD-related molecular alterations, and that cobimetinib may contribute to immune modulation in TNBC.

Biochar-based cathodes for bioelectro-Fenton systems: Design strategies, electrocatalytic mechanisms, and environmental applications - Shu-Hui Liu; Chung-Yen Yeh; Wei-Tzu Huang; Yi-Chun Yu; Chi-Wen Lin (Journal of Environmental Chemical Engineering, 2026)

Interface-engineered amorphous coatings for plasmon-enhanced charge separation in Ag/TiO2 photocatalysts - Tsung-Lin Yang; Yu-Kai Zhou; Pei-Kai Hsu; Chi-Liang Chen; Shih-Yun Chen (Journal of Environmental Chemical Engineering, 2026)

Immune response as a modifier linking phthalate exposure to lung function decline: Results from a longitudinal study - Wei-Chi Wang; Yuan-Ting C. Lo; Hsiu-Ying Ku; Hsu-Kai Huang; You-Zhen Chen; Wei-Yu Lin; Han-Bin Huang (Environmental Pollution, 2026)

Multiplexed EDL-FET biosensor with tannic acid stabilization for simultaneous p-Tau217 and Aβ42/Aβ40 detection in plasma and whole blood from stroke patients - Shang-Chi Chien; I-Yin Chang; Yong-Chuan Chen; Yi-Zhen Lai; Yu-Fang Chen; Pei-Lun Sun; Bor-Ran Li; Yu-Lin Wang; Jung-Chih Chen (Analytica Chimica Acta, 2026)

Multiscale drivers of arthropod functional guilds in rice agroecosystems: Evaluating the roles of climatic, landscape, and management factors - Yu-Pin Lin; Pei-Chen Lin; Shafira Wuryandani; Chun-Chia Liu; Chiao-Ming Lin; Chi-Wei Tsai; Chi-Lun Huang; Chuan-Kai Ho; Gerard H. Ros (Agriculture, Ecosystems & Environment, 2026)

Genome-wide association analysis for resistance against iridovirus disease in large yellow croaker (Larimichthys crocea) from a natural outbreak population - Ying Pan; Hongshu Chi; Nengfeng Lin; Junjia Zeng; Xiaodong Liu; Xiuxia Chen; Zaiyu Zheng; Qiuhuan Jiang; Xunkai Yu; Hui Gong (Fish & Shellfish Immunology, 2026)

Piezo-coupled triboelectric self-powered tactile sensor based on a self-healable polymer for object recognition - Manikandan Venkatesan; Wei-Wen Chen; Yu-Chen Wang; Yung-Chi Hsu; Jayashree Chandrasekar; Hao-Yuan Chen; Shih-Yu Lin; Chia-Jung Cho; Shang-Jui Huang; Ming-An Chung; Wen-Ya Lee; Yu Wen; et al. (Chemical Engineering Journal, 2026)

Self-powered trickling-filter bioelectro-Fenton removal of gaseous isopropanol using sulfur-modified Fe-biochar fillers and a melanin-modified cathode - Chi-Wen Lin; Yu-Sheng Yang; Shu-Hui Liu; Wei Tong Chen; Xiang-En Ke (Chemical Engineering Journal, 2026)

A chitosan-based cinnamaldehyde–raspberry ketone integrated carrier architecture for oral delivery toward mild metabolic regulation - Yu-Chi Wang; Sin-Huei Chuang; Chien-Fu Lin; Yan-Ting Lin; You-Song Cheng; Chih-Chen Lin; Chi-Chen Ting; Wei-Han Chen; Ting-Yu Chen; Shen-Ho Kuo; Fu-I Tung; Tse-Ying Liu (Carbohydrate Polymers, 2026)

Exposure-informed ventilation control for nanoparticle pollutants in an enclosed industrial built environment: A laser metal deposition case study - Ying-Fang Wang; Thi-Cuc Le; Jing Wang; Yu-Tung Dai; Phuong-Uyen Tran; Van-Nghia Tran; Guo-Ping Chang-Chien; Lin-Chi Wang (Building and Environment, 2026)

A dual colorimetric and fluorescent sensor for non-enzymatic glucose detection via catalytic reaction with o-phenylenediamine mediated by carbon dot-decorated Fe3O4 nanoparticles - Wei-Bin Tseng; Wei-Kai Tsai; Ming-Mu Hsieh; Chi-Yu Lu; Po-Chiao Lin; Wei-Lung Tseng (Analytica Chimica Acta, 2026)

Weather source heterogeneity affects disease forecasting: A case study of rice bacterial leaf blight in Taiwan - Jie-Hao Ou; Guo-Cih Lin; Yea-Fang Wu; Chi-Yu Chen; Guan-Ying Huang; Hau-Ping Chou; Chien-Chih Kuo; Hsin-Yuh Wu; Qiao-Juan Lai; Chih-Wei Wang; Yi-Chen Tsai; Chang-Hsin Kuo; et al. (Agricultural and Forest Meteorology, 2026)

Late Holocene human-environment interactions on a small island of the Taiwan Strait - Ranjan Kumar Mohanty; Abdur Rahman; Yi-Chen Ho; Yu-Chen Lu; Cheng-Tao Lin; Hung-Chun Chao; Ling-Ho Chung; Chin-Yung Chao; Liang-Chi Wang (Quaternary International, 2026)

FBG-based dynamic characterization of a scaled offshore wind turbine foundation model under impact and recorded seismic excitations - Jui-Chi Lin; Yi-Lun Liao; Bor-Yann Chen; I-Hsin Chiu; Wan-Yu Xu; You-Chen Liao; Yi-Heng Yang; Yu-Hsi Huang (Ocean Engineering, 2026)

Motion prediction of an unpowered autonomous underwater vehicle under wave conditions using hybrid CFD–LSTM model - Yu-Hsien Lin; Cheng-Chi Shi; Muk Chen Ong (Ocean Engineering, 2026)

Differential thermal sensitivity among shallow-water octocorals and its association with holobiont composition - Hsien-Yu Cheng; Yu-Chien Wang; Yan-Zhen Meng; Chien-Yi Wu; An-Chi Liu; Yen-Chih Lin; Jui-Hsun Hung; Shan-Hua Yang (Marine Environmental Research, 2026)

Invisible plastic release from overlooked usage practices in microwaved food packaging - Pei-Ying Lin; Shu-Ling Hsieh; I-Hsuan Wu; Yu-Chi Hsieh; Shuchen Hsieh (Food Chemistry, 2026)

Caffeinated chewing gum improves military performances in special forces soldiers - Yi-Jie Shiu; Che-Hsiu Chen; Hung-Yu Lin; Chia-Cheng Yang; Chi-Wen Yen; Han-Yuan Chang; Hsuan-Ta Chen; Chih-Hui Chiu (European Journal of Applied Physiology, 2026)

Topical delivery of Lidocaine using spicules for local anesthesia - Chi Zhang; Ping Yang; Xueke Lin; Huijung Lai; Yi Liu; Shifeng Yu; Tszyam Liu; Ming Chen; Yongxiang Huang (Drug Delivery and Translational Research, 2026)

A 44-min periodic radio transient in a supernova remnant - Di Li; Mao Yuan; Lin Wu; Jingye Yan; Xuning Lv; Chaowei Tsai; Pei Wang; Jiaqi Zhao; Weiwei Zhu; Li Deng; Ailan Lan; Renxin Xu; et al. (Science Bulletin, 2026)

Piezo-photocatalysis with BaTiO3 nanorod arrays–Ag nanoparticle composites for the photodegradation of rhodamine B - Yen-Lun Chiu; Thi Nghi Nhan Nguyen; Hsin-Yu Chi; Heng-Jun Lin; Kao-Shuo Chang (Journal of Environmental Chemical Engineering, 2026)

Integrated transcriptomic and functional analyses provide insights into the heat stress response mechanisms and HrcA mediated potential regulatory in Tetragenococcus halophilus JY1 - Fangming Lan; Yu Zhang; Chi Zhao; Jiayi Lin; Dongdong Sun; Juliang Dai; Lixin Luo (Food Bioscience, 2026)

A case study on indoor air quality assessments and health risk implications across diverse university environments - Jheng Fong Tsai; Yu-Hsiang Cheng; Zong-Rong Chen; Chi-Chi Lin (Atmospheric Pollution Research, 2026)

Doxorubicin-Induced Cardiotoxicity in Breast Cancer: Mechanistic Pathways, Pharmacogenomic Modifiers, and Translational Strategies - Chi-Tong Kuok; Hao-Wei Lee; Chen-Yu Huang; Yu-Che Cheng; Shih-Chang Lin; Jiun-Wen Guo (Cardiovascular Toxicology, 2026)

Green synthesis of glycerol carbonate from glycerol and CO2 using a polymeric ionic liquid catalyst: An experimental and theoretical study - Yi-Lin Lee; Yu-Chi Kao; He-Xiang Xu; Shun Tsunekawa; Masaaki Yoshida; Yi-Pei Li; Chechia Hu (Journal of Cleaner Production, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Microbial-assisted copper migration stabilizes Fe/Cu cathodes for long-term bioelectro-Fenton degradation of bisphenol A - Chi-Wen Lin; Yu-Cheng Chiang; Hui Suan Ng; Shu-Hui Liu; Yi-Kai Yang (Journal of Environmental Chemical Engineering, 2026)

Corrigendum to “AI-driven process-tolerant BioFET sensing model for precise biliary atresia diagnosis of infants with a single drop of blood” [Chem. Eng. J. (2026), volume 531, 1 March 2026, 173939] - Chia-Kai Lin; Chi-Ming Ku; Chia-Che Wu; Yi-Fang Wu; Huey-Ling Chen; Yueh-Ju Hou; Arnab Pal; Zong-Hong Lin; Chee-Seng Lee; Tzong-Rong Ger; Yu-Lin Wang (Chemical Engineering Journal, 2026)

REAL208, a Liposome-based Formulation of Phosphodiesterase Inhibitor, Protects Acute Kidney Deficiency in Mice - Jui-Chi Tsai; Yi-Wen Lin; Chun-Yao Huang; Chun-Ming Shih; Yu-Tse Wu; Toshio Kurosaki; Yuki Inoue; Ying-Chi Du; Feng-Yen Lin (Pharmaceutical Research, 2026)

Sex Differences in Vigilance Functions of Golden Snub-nosed Monkeys (Rhinopithecus roxellana): Females Prioritize Antipredator Vigilance While Males Focus on Social Vigilance - Hui Yu; Chi Zhang; Jinhuang Lin; Ruiyuan Li; Hui Yao; Wanji Yang; Ali Krzton; Yang Yu; Zuofu Xiang (International Journal of Primatology, 2026)

Intelligent circuit exercise training improves platelet mitochondrial bioenergetic efficiency in sedentary men - Ai Yin Lim; Chi-Yao Chiang; Yu-Ting Lin; Chih-Chin Hsu; Jong-Shyan Wang (European Journal of Applied Physiology, 2026)

Effect of somatosensory games on arterial stiffness and antioxidant status in postmenopausal women - Yi-Hung Liao; Kunanya Masodsai; Yu-Chi Kuo; Hsiao-Kuan Wu; Yi-Yuan Lin (European Journal of Applied Physiology, 2026)

Zebrafish Model Reveals Early Electrocardiographic and Molecular Signatures of Doxorubicin-Induced Cardiotoxicity - Zih-Yin Lai; Chi-Ying Lee; Yu-Ching Chiu; Chia-Hung Lin; Chung-Chi Yang; Chia-Chia Ho; Lawrence Yu-Min Liu; Yung-Jen Chuang (Cardiovascular Toxicology, 2026)

Inhibitory activity of dehulled adlay extrudate against ethanol-induced gastric mucosal injury and stability tests of active indicative components - Ming-Yi Lee; Shih-Min Hsia; Ching-I Lin; Yu-Chia Chang; Yi-Hsiang Liang; Lu-Chi Chan; Ju-Tsui Lin; Yi-Fen Chiang; Wei-Chih Sun; Cheng-Pei Chung (Journal of Cereal Science, 2026)

Improvement of indoor air quality and health effects in COPD patients in a heavy industrial area - Jia Lin Zhang; Yi Ting Chang; Ching Yu Hsiao; Chung-Shin Yuan; Yen-Ping Peng; Da Wei Wu; Huang-Chi Chen; Jia-Yu Kuo; Huai-Lei Juan; Pei-Shih Chen (Environmental Research, 2026)

Metabolomics-based investigation of PFOS-induced molecular perturbations across multiple rat organs - Tzu-Hsin Yen; Sheng-Han Lee; Hao-Jan Liang; Zou-Xiao Huang; Chi-Tsung Chen; Christopher Li; Ching-Yu Lin (Environmental Toxicology and Pharmacology, 2026)

AI-driven process-tolerant BioFET sensing model for precise biliary atresia diagnosis of infants with a single drop of blood - Chia-Kai Lin; Chi-Ming Ku; Chia-Che Wu; Yi-Fang Wu; Heuy-Ling Chen; Yueh-Ju Hou; Arnab Pal; Zong-Hong Lin; Chee-Seng Lee; Tzong-Rong Ger; Yu-Lin Wang (Chemical Engineering Journal, 2026)

TEDD 2.0: an advanced temporal gene expression database enabled by in-silico functional analyses for developmental mechanism investigation - Chi Chun Chan; King Kin Lam; Lin Chen; Mingyang Yu; Jingwen Hu; Yujie Zhu; Yuting Zheng; Jia Zheng; Kwong Wai Choy; Zirui Dong (Science China Life Sciences, 2026)

Role of ITIH4 in Modulating YAP/TAZ-Mediated Apoptosis of Type II Alveolar Epithelium during Acute Respiratory Distress Syndrome - Yu-Syuan Shih; Xiao-Yue Chen; Yi-Wei Lin; Zih-An Liao; Yi-Hsuan Liu; Vincent Laiman; Syue-Wei Peng; Kazuhiro Ito; Hsiao-Chi Chuang (Pharmaceutical Research, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Toxicophore-informed machine learning integrating Tox21 assay readouts for organ system–specific carcinogenicity prediction - Chi-Yun Chen; Wei-Chun Chou; Venkata Nithin Kamineni; Pei-Yu Wu; Zhicheng Zhang; Xue Wu; Chris D. Vulpe; Zhoumeng Lin (Environmental Pollution, 2026)

Sonofoam: An ultrasound-responsive foam for broad pleural coverage and sonoporation-enhanced drug delivery in pleurodesis - Hsin-Yi Lin; Wei-Chih Liao; Yun-Chieh Lin; Hsin-Chin Li; Min-Yu Tsou; Bo-Tai Cheng; Yu-Nan Huang; Ulziijargal Sukhbat; Chun-Yi Chiang; Chi-Fen Chuang; Zong-Han Hsieh; Chih-Yen Tu; et al. (Chemical Engineering Journal, 2026)

Coupled oxygen and nitrogen defect sites in Co-N4-coordinated frameworks facilitate stepwise CO2 methanation - Pin-Yu Liu; Sheng-Xiang Chou; Wei-Tse Sun; Hsin-Han Chen; Cheng-Hung Tsai; Yen-Lin Lai; Yu-Cheng Shao; Chi-Liang Chen; Yu-Ching Huang; Yun-Wei Chiang; Bo-Hong Liu; Chia-Hsin Wang; et al. (Chemical Engineering Journal, 2026)

Shifting drivers of lake ecology in northern Taiwan over the last 1800 years: From climate variability to human land-use change - Abdur Rahman; Yu-Xiong Chen; Jo-lin Lai; Ranjan Kumar Mohanty; Bushra Khatoon; Kaoru Kashima; Liang-Chi Wang (CATENA, 2026)

Optical properties of dissolved organic matter play pivotal roles in mediating trace metal forms in a mangrove-dominated tidal estuary - Keisuke Nakayama; Meng-Chi Hung; Chih-Yu Chiu; Sen-Lin Tang; Mei-Li Hsueh; Chin-Ching Wu; I-Hao Hung; Ya-Hsin Liu; Jeng-Wei Tsai (Marine Pollution Bulletin, 2026)

ER stress disrupts MFN2-related mitophagy via HRD1-PINK1/ parkin axis in bovine embryos - Shu-Ming Shi; Li-Ying Liu; Zhi-Chao Chi; Lin-Yi Qu; Jing-Hang Li; Guan-Lin Jia; Yu-Yan He; Yong-Xun Jin; Ming-Jun Zhang; Xian-Feng Yu (Theriogenology, 2026)

Dual-function microalgal microbial fuel cell for simultaneous wastewater remediation and bioelectricity generation under magnetically stirred cathode configuration - Chi-Wen Lin; Shu-Hui Liu; Yu-Shen Cheng; Baala H. Anandapadmanaban (Journal of Water Process Engineering, 2026)

Modified QuEChERS coupled with hybrid mass spectrometry for 322 target pesticides and suspect screening of emerging organic contaminants in agricultural soils - Yu-Hui Chang; Chi-Chieh Hu; Chinn-Yuan Fu; Sichao Wang; Yu-Min Tzou; Shiou-Ruei Lin; Hsiao-Ying Yang; Jerry J. Wu; Cheng-Hua Liu; Ya-Hui Chuang (Journal of Hazardous Materials, 2026)

Dibifree, a dietary phytomix, improves glycemic control and adiposity via modulation of the gut–pancreas–adipose–immune axis in type 2 diabetes - Tzu-Yi Huang; Niann-Tzyy Dai; Hsiu-Jung Liao; Ly Hien Doan; Tai-Shan Cheng; Wen-Yu Hsieh; I-Hsuan Lin; Yu-Tang Huang; Chia-Ching Liaw; Hsiao-Sheng Liu; Wei-Ming Cheng; Chun-Li Su; et al. (Food Research International, 2026)

Electrochemically activated polypyrrole for full-polymer electrochemical deionization: Unraveling potential-gated ion exchange behavior and its application to oxyanion removal - Hung-Yi Huang; Yi-Heng Tu; Yi-An Chen; Cheng-Wei Lin; Yu-Hung Cheng; Hsing-Mei Chou; Yu-Hsiang Yang; Yun Ku; Zhiyin Yang; Sophia Uemura; Hsin-Lung Chen; Richard B. Kaner; et al. (Chemical Engineering Journal, 2026)

Isomeric halide engineering of self-assembled hole-selective layers for efficient indoor perovskite photovoltaics - Zhong-En Shi; Yi-Ting Hong; Cheng-Chieh Lu; Po-Cheng Shih; Shih-I Lu; Hsiao-Chi Hsieh; Sie-Rong Li; Yu-Che Lin; Zheng-Xuan Cai; Yan-Duo Lin; Chih-Ping Chen (Chemical Engineering Journal, 2026)

A machine learning and box modeling approach to comparing the atmospheric chemistry of high- and low-ozone and PM₂.₅ episodes - Ahsan Mozaffar; Yan-Lin Zhang; Yihang Hong; Mei-Yi Fan; Yu-Chi Lin (Atmospheric Research, 2026)

AMPK Activation by ENERGI Ameliorates Behavioral and Synaptic Deficits in a Mouse Model of Autism - Ming-Chia Chu; Chi-Chun Wu; Yueh-Jung Chung; Chieh-Yu Chang; Han-Fang Wu; Sze-Chi Tsai; Tzu-Ning Peng; Tzu-Jung Yang; Hui-Ching Lin (Molecular Neurobiology, 2026)
Autism spectrum disorder (ASD), a neurodevelopmental disorder, is characterized by synaptic dysregulation as its underlying pathophysiological mechanism. AMP-activated protein kinase (AMPK), an intracellular energy sensor, plays a pivotal role in regulating synaptic integrity and function. Current treatments for ASD exhibit limited benefits in alleviating the core symptoms of ASD. Consequently, we investigated the therapeutic potential of ENERGI, a novel AMPK-activating compound, in a valproate (VPA)-induced mouse model of ASD. ENERGI was administered via drinking water to VPA-induced ASD offspring. After 7 days of treatment, ENERGI gradually alleviated social defects, repetitive behaviors, and emotional comorbidities in VPA-induced ASD offspring. At the synaptic level, ENERGI treatment restored aberrant plasticity, spine structure, and dendritic arborization in the hippocampus of VPA-induced ASD offspring. Notably, the curative effects of ENERGI in VPA-induced ASD offspring were equivalent to those of D-cycloserine (DCS), a known therapeutic candidate for ASD. Moreover, ENERGI demonstrated superior efficacy in restoring spine abnormalities than DCS. Mechanistically, 7-day ENERGI treatment reversed the reduction in AMPK phosphorylation, and normalized the elevated PSD95 and synaptic GluA2 levels in VPA-induced ASD offspring, whereas DCS treatment only rescued the synaptic GluA2 levels. Overall, these findings suggest that AMPK activation by ENERGI effectively reverses behavioral and synaptic deficits in a preclinical ASD model, supporting AMPK as a promising target for developing novel ASD therapies.

Strategies for Promoting Sustainable Development of Land and Water Resources in a Land Subsidence Affected Area of Taiwan - Chung‐Feng Ding; Yu‐Ching Lin; Reuy‐Chi Kao (Irrigation and Drainage, 2025)
Land subsidence has been observed in many parts of the world. In Taiwan, the main cause is the excessive extraction of groundwater in alluvial plains. For limited land and water resources, it is essential to balance the development among economics, society and conservation issues in land subsidence‐affected areas. The Taiwan government promotes ‘prevention (non‐engineering)’ and ‘reclamation (engineering)’ strategies since the 1980s, which are to increase surface and alternative water supply, decrease groundwater abstraction, strengthen groundwater recharge, enhance enforcement related to water resources utilization and management, reduce induced disasters and encourage public participation. This paper reports the framework of prevention and reclamation strategies and their relative achievements; furthermore, it recently integrated ICT technology with low‐cost devices to monitor the regional pumping behaviour related to land subsidence for groundwater management. The real‐time monitoring system enables the utilization of groundwater more effectively and sustainably in reducing land subsidence. In 2022, according to the delimited goals of each strategy in every phase, all achievements were effective in mitigating the annual subsiding rate and affected area, the former from over 20 cm/year down to 8 cm/year, the latter from 1616 to 310 km 2 .

Identification and quantification of per- and polyfluoroalkyl substances in wastewater from Taiwan using targeted and non-targeted approaches - Jen-Yi Hsu; Chih-Wei Chang; Yu-Wen Lin; Yuan-Chih Chen; Pao-Chi Liao (Chemosphere, 2025)

Potential anti-H1N1 schitriterpenoids from Kadsura japonica L. vines - Hung-Tse Huang; Chun-Tang Chiou; Yu-Chi Lin; Li-Jie Zhang; Chih-Hua Chao; Ping-Jyun Sung; Jih-Jung Chen; Tsung-Lin Li; I-Wen Lo; Chia-Ching Liaw (Phytochemistry, 2025)

Exploring the potential antimicrobial ability of Lactiplantibacillus plantarum against common fish pathogens - Ting-Chang Lin; Yu-Chi Wu (Fish & Shellfish Immunology, 2025)

Torenia concolor exhibits antiviral activity against fish nodavirus and iridovirus - Zhe-Li Lin; Yu-Chi Wu (Fish & Shellfish Immunology, 2025)

Alkylammonium ligands-driven perovskite lattice engineering for white perovskite nanocrystals single emitters - Jean-Sébastien Bénas; Zhen-Li Yan; Wei-Cheng Chen; Chu-Chen Chueh; Jing-Yan Wu; Wei-Wen Chen; Fang-Cheng Liang; Erdi Akman; Yu-Jung Lu; Yen-Yu Wang; Ja-Hon Lin; Ye Zhou; et al. (Chemical Engineering Journal, 2025)

Downlisting and recovery of species assessed by the IUCN - Mu‐Ming Lin; Richard A. Fuller; In‐Ki Kwon; Kisup Lee; Simba Chan; Wangwang Qiu; Yat‐Tung Yu; Chi‐Yeung Choi (Conservation Biology, 2025)
Despite the increasing number of species assessed for extinction risk by the International Union for Conservation of Nature (IUCN) (163,040 species as of 2024), only about 1 in 1,000 have been downlisted due to genuine population improvement. Although this rare conservation achievement has been widely celebrated in several recent cases, some other downlisting decisions have met with controversy. A primary role of the IUCN is to assess extinction risk. In this role, it must maintain its independence and not be influenced by the public outcry that may occur when a high‐profile species is downlisted, even if well‐established conservation programs may be disrupted or abandoned as a result. We explored the potential positive and negative consequences of downlisting for conservation efforts through case studies of the giant panda ( Ailuropoda melanoleuca ), red‐crowned crane ( Grus japonensis ), saiga antelope ( Saiga tatarica ), and black‐faced spoonbill ( Platalea minor ), which has recently been proposed for downlisting. Although downlisting can enable more effective use of limited resources, these cases highlight potential risks, including weakened legal backing, diversion of resources away from the species, and declining public and political support. The relatively unquestioned downlisting of the saiga antelope illustrates how early and inclusive engagement of local experts, assessors, donors, and other stakeholders can help ensure that decisions are effectively communicated and implemented without jeopardizing species recovery. The IUCN Green Status of Species assessment is a complementary tool to the IUCN Red List and offers a useful measure of conservation progress, which can help decision makers ensure that downlisting does not undermine long‐term conservation efforts.

Using an acidic vesicle tracer to identify potential bacterivores in coastal waters of the subtropical Western Pacific Ocean - Yun-Chi Lin; Yu-Chen Lin; Kuo-Ping Chiang; Chien-Pang Chin; Wen-Chen Chou (Frontiers in Marine Science, 2025)
Bacterivores play a key role in transferring energy through microbial food webs and are broadly classified as heterotrophic or mixotrophic based on the presence of inherent chloroplasts. Mixotrophs, especially in low-latitude regions, have recently gained attention due to their dual roles as primary producers and bacterial grazers, which enable them to thrive in nutrient-poor, stratified waters where traditional autotrophs or heterotrophs may be less competitive. This study investigated the composition of bacterivores in the coastal waters of northeastern Taiwan during the warm season (July and August 2022). A combination of LysoTracker staining, flow cytometry sorting, and 18S rRNA gene amplicon sequencing was used to rapidly identify heterotrophic and mixotrophic nanoflagellates (HNFs and MNFs, respectively) based on chloroplast autofluorescence. The dominant eukaryotic lineages included Alveolata, Stramenopiles, Opisthokonta, Chlorophyta, and Rhizaria. HNFs were primarily composed of MAST clades, choanoflagellates (Opisthokonta), Telonemia, and Radiolaria, while MNFs included cryptophytes, haptophytes, and chlorophytes such as Mamiella , Mantoniella and Tetraselmis , as well as stramenopiles like Dictyochophyceae and Chrysophyceae. Notably, several non-motile chlorophytes, including Chloropicon and members of Pycnococcaceae, were identified as potential bacterivores based on Lysotracker signals; however, their phagotrophic capability requires further confirmation in future studies. Despite the limitations of LysoTracker-based methods, this study reveals previously overlooked mixotrophic diversity and highlights the need for further validation. These findings advance our understanding of carbon flow and microbial dynamics in subtropical marine ecosystems under changing environmental conditions.

The connection between skeletal muscle and spinal canal membrane of Takifugu rubripes and its anatomical and physiological significance - Yang Song; Wen-Bin Jiang; Yu-Yu Xiong; Chun-Zhuo Shi; Hua-Xun Lai; Jing-Xian Sun; Lin-Lin Chen; Bo Liu; Yan-Yan Chi; Ji-Hang Li; Yi-Tong Sun; Xu-Hui Zhang; et al. (Frontiers in Marine Science, 2025)
Introduction The myodural bridge (MDB) is considered one of the circulatory dynamics of cerebrospinal fluid (CSF). Initially identified in the human neck, it has since been documented across diverse vertebrates, including fish with analogous “MDB-like” structures. The teleost Takifugu rubripes , which exhibits a high degree of genetic homology with humans, serves as an excellent model for such comparative studies. Investigating its MDB-like structure can therefore provide a morphological basis for elucidating the mechanism of CSF circulation and its evolution during the vertebrate land–water transition. Methods In this study, the morphology, development, and ultrastructure of MDB-like structure of Takifugu rubripes were explored. Three fresh adult T. rubripes were selected for gross anatomy. After incubation, 33 T. rubripes aged 13–120 days after hatching (dah) were fixed in 10% formalin solution. The samples aged 50–120 dah were further decalcified with EDTA for histological paraffin sectioning and Masson staining. Four cases aged 106 dah were fixed with 2.5% glutaraldehyde, two of which were observed by scanning electron microscopy, and two cases were observed by transmission electron microscopy. Results Through light microscopy and electron microscopy, the results of the current study is that there are three types of fiber connections (MDB-like) between skeletal muscle and the spinal canal membrane in T. rubripes : (1) The fibers from the myocomma attach to the spinal canal membrane; (2) The epimysium connects to the spinal canal membrane directly or connects to the spinal canal membrane through reticular, filamentous fibers, or fibers emitting from the perimysium; and (3) The fibers from the end of the muscle bundle stop at the spinal canal membrane. These connections mainly exist on the sides of each vertebral interspace and may function similarly to the MDB. Discussion Developmentally, “MDB-like” structures appeared in T. rubripes hatched at 18 dah, began to transmit force at 21 dah, and may have a positive correlation in development with the muscle and spinal canal membrane. This experiment provides developmental morphological information for comparative studies on the conservation and interspecies differences of MDB in evolution and provides informational support to explore the physiological function of MDB in humans.

Salidroside improves bovine embryo quality by mitigating oxidative stress and regulating mitochondrial lipid metabolism - Li-Ying Liu; Xian-Feng Yu; Zhi-Chao Chi; Shu-Ming Shi; Tian Lan; Jia-Hui Leng; Jing-hang Li; Yu-Yan He; Lin-Yi Qu; Guan-Lin Jia; Ilkeun Kong; Ming-Jun Zhang; et al. (Theriogenology, 2025)

Geotechnical reconnaissance of Hualien Port after the 2024 ML 7.2 hualien earthquake - Hsuan-Chih Yang; Chun-Jia Huang; Yung-Yen Ko; Kuan-Yu Chen; Chi-Chin Tsai; Chun-Hung Lin; Yu Wei Hwang; Min-Chien Chu; Yu-Syuan Jhuo; Yu-Ting Hsueh; Shodai Okano; LeeYi Wang; et al. (Soil Dynamics and Earthquake Engineering, 2025)

Long-term organic fertilization reduces cadmium bioavailability via enhanced binding to organic fractions and Fe-bearing minerals - Zhi-Lai Chi; Qiang-Long Hu; Lin Shi; Fu-Sheng Sun; Jun Wang; Guang-Hui Yu (Journal of Hazardous Materials, 2025)

Linking source-to-sink processes, organic matter composition, and oxygen consumption on a shallow passive margin shelf sustained by small mountainous rivers - Yu-Shih Lin; Chih-Lin Wei; Yuan-Pin Chang; Jih-Terng Wang; Shu-Ying Chuang; Liang-Chi Wang; James T. Liu; Hong-Chun Li; Chieh-Wei Hsu (Geochimica et Cosmochimica Acta, 2025)

Collagen peptides from Skipjack tuna (Katsuwonus pelamis) bones: Composition, characterization, and mechanism of high-fat diet-induced NAFLD amelioration - Yu-Lin Jiang; Shuang-Yi Zhang; Bin Wang; Yu-Hui Zeng; Li Xu; Chang-Feng Chi (Food Research International, 2025)

Spatiotemporal variations and risks assessment of PAH-bound suspended particles across different Asian countries: Insights from multi-city sampling and source apportionment - Kai Hsien Chi; Yen-Shun Hsu; Sheng-Lun Lin; Charles C.-K Chou; Somporn Chantara; Sereeter Lodoisamba; Thi Tuyet-Hanh Tran; Delgerzul Lodoisamba; Yuan Cheng Hsu; Chih-Da Wu; Tuan Hung Ngo; Shih Yu Pan (Environmental Research, 2025)

Microfluidic device for high-throughput cancer drug screenings - Po-Hsun Chen; Lin-Yu Wang; Chia-Yuan Chang; Yuh-Shiuan Chien; Yu-Chia Su; Chi-Kuang Wang; Kuang-Chong Wu; Hsian-Jean Chin; Chien-Fu Chen (Chemical Engineering Journal, 2025)

Sugar-based block copolymer/carbon nanotube nanocomposites for thermoelectric applications - Yen-Yu Chen; Hong Li; Chih-Jung Lin; Koshin Tanaka; Meng-Hao Lin; Shao-Huan Hong; Min-Chi Fu; Jian-Fa Ding; Yu-Jane Sheng; Redouane Borsali; Tsuyohiko Fujigaya; Cheng-Liang Liu (Chemical Engineering Journal, 2025)

Contrasting char-EC and soot-EC in sources, atmospheric processing, and light-absorbing capabilities: Insights from high-resolution stable carbon isotope analysis - Mingyuan Yu; Yu-Chi Lin; Feng Xie; Fang Cao; Yan-Lin Zhang (Atmospheric Research, 2025)

Elucidating the suppressive role of native bacterial traits against root-knot nematodes to control plant-parasitic effect in serpentine hostile rhizosphere soil - Aslia Asif; Liang-Yu Lin; Ping-Chi Hsu; Suprokash Koner; Zeng-Yei Hseu; Tsui-Kang Hsu; Shih-Wei Huang; Bing-Mu Hsu (Applied Soil Ecology, 2025)

Anti-cancer effect of Willughbeia edulis Roxb. Stem extract in hepatocellular carcinoma cells through triggering apoptosis and G2/M cell cycle arrest - Thi Tuyet Nhung Nguyen; Yu-Chi Lin; Ching-Kuo Lee; Jing-Jy Cheng (Phytochemistry Letters, 2025)

Discovery of a new 1-monoglyceride from Streptomyces albogriseolus JM128 symbiotic with Lendenfeldia sponge - Yun-Ting Zeng; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; You-Ying Chen; Li-Guo Zheng; Chih-Yin Huang; Hsi-Wen Sun; Ping-Jyun Sung (Phytochemistry Letters, 2025)

Microwave-extracted insect melanin as a metal chelator for bimetallic bioelectro-fenton cathodes: A sustainable approach to ibuprofen-contaminated wastewater treatment - Shu-Hui Liu; Hui-Yu Tang; Chi-Wen Lin; Wei-Jun Lai (Chemical Engineering Journal, 2025)

A novel approach for quantifying therapeutic monoclonal antibodies in blood through liquid chromatography–tandem mass spectrometry - Tsun-Hao Chi; Chiao Lo; Shin-Yi Lin; Yi-Hsin Liang; Wen-Chi Chang; Chia-Yu Yeh; Huai-Hsuan Chiu; Ching-Hua Kuo (Analytica Chimica Acta, 2025)

Unveiling Unusual Ecofunctional Traits of Endozoicomonas Species Through Comprehensive Comparative Genomics - Sim Lin Lim; Ching‐Hsiang Chin; Yu‐Jing Chiou; Ming‐Tsung Hsu; Pei‐Wen Chiang; Hsing‐Ju Chen; Yung‐Chi Tu; Wen‐Shyong Tzou; Sen‐Lin Tang (Environmental Microbiology, 2025)
Endozoicomonas is an omnipresent marine bacterial genus, associated with various marine organisms, that contributes to host health, nutrient cycling and disease resistance. Nonetheless, its genomic features remain poorly characterised due to a paucity of high‐quality genomes. In this study, we sequenced 5 novel Endozoicomonas strains and re‐sequenced 1 known strain to improve genomic resolution. By integrating these 6 high‐quality genomes with 31 qualified published genomes, our pan‐genomic analysis revealed variation in genetic traits among clades. Notably, Endozoicomonas lacks quorum‐sensing capabilities, suggesting resistance to quorum quenching mechanisms. It also lacks the capacity to synthesise and transport vitamin B12, indicating that it does not supply this nutrient to holobionts. Remarkably, Endozoicomonas genomes encode 92 identified giant proteins (15–65 kbp). These proteins cluster into three major groups associated with antimicrobial peptide synthesis, exotoxin production and cell adhesion. Additionally, we found that Endozoicomonas has acquired prophages from diverse sources via infection or other types of gene transfer. Notably, CRISPR‐Cas sequences suggest evolutionary trajectories independent of both prophage acquisition and phylogenetic lineage, implying potential geographic influences or environmental pressures. This study provides new insights into the genomic diversity of Endozoicomonas and its genetic adaptations to diverse hosts.

Integrating machine learning and metabolomics to uncover new biomarkers for predicting pesticide exposure among patients with kidney function decline - Junne-Ming Sung; Yu-Chi Hung; Wan-Ru Wang; Chiau-Jun Chu; Yen-Ping Lin; Kuan-Hung Liu; Trias Mahmudiono; Hsiu-Ling Chen (Science of The Total Environment, 2025)

Corrigendum to “Active and intelligent gellan gum-based packaging films for controlling anthocyanins release and monitoring food freshness” [Carbohydrate Polymers 254 (2021) 117410] - Li-Ting Wu; I-Lin Tsai; Yi-Cheng Ho; Yu-Hao Hang; Chi Lin; Min-Lang Tsai; Fwu-Long Mi (Carbohydrate Polymers, 2025)

Novel xylanase activity and biofuel production in Lacrimispora xylanolytica isolated from termite guts symbionts - Chia-Chi Yang; Yu-Ju Lin; Fu-Shyan Wen (Bioresource Technology, 2025)

Mercury flows in a cement plant adopting circular economy policies - Liang Yu Chen; Chia Chi Hsu; Chin Lung Lin; Ming Lun Lu; Hung Lin Chiang; Moo Been Chang (Waste Management, 2025)

A numerical study of NO removal from exhaust gas at low-temperature using metal Zeolite catalysts - Way Lee Cheng; Ding-Hui Wang; Yi-Chi Chang; Pei-Cheng Cheng; Yu-Zheng Wang; Yuan-Chung Lin (Fuel, 2025)

Tailoring Cu3Nx clusters on TiO2 nanosheets to the sub-nanometric scale for enhancing NH3 photosynthesis - Hyun Sik Moon; Yu-Jeong Yang; Getasew Mulualem Zewdie; Geon Youn; Yi-An Chen; Yu-Peng Chang; Kai-Chi Hsiao; Ting-Han Lin; Yi-Dong Lin; Jun Kue Park; Jucheol Park; Yan-Gu Lin; et al. (Chemical Engineering Journal, 2025)

Pixel array-based urine biosensor for detection of trimethylamine N-oxide and glucose for early detection of diabetic kidney disease - Mei-Ching Yu; Chi-Jen Lo; Wei-Cheng Lin; Wei-Lun Yen; Yun-Yu Hsieh; Bing-Hong Chen; Fu-Sung Lo (Analytica Chimica Acta, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Origin and metamorphism of ophiolitic serpentinites from the Yuli belt, eastern Taiwan: new findings and tectonic implications - Dominikus Deka Dewangga; Chin-Ho Tsai; Yoshiyuki Iizuka; Ilona Talvikki Sakaguchi; Yui Kouketsu; Sun-Lin Chung; Chi-Yu Lee; Wen-Yen Chang; Huei-Fen Chen (International Geology Review, 2025)

Dietary supplementation with Pediococcus pentosaceus promotes resistance to betanodavirus and ranavirus in giant groupers - Chun-Kuei Chang; Zhe-Li Lin; Yu-Hsuan Kai; Mu-Yun Peng; Yu-Chi Wu (Aquaculture, 2025)

Microplastic contamination in the gastrointestinal tracts of larval fish assemblages from coastal waters in southwestern Taiwan - Ming-Yih Leu; Sun-Hon Lin; Te-Yu Chen; Fung-Chi Ko; Shao-Hung Peng (Regional Studies in Marine Science, 2025)

Junceellolide Q, a new polyacetoxybriarane from the delicate sea whip octocoral Junceella fragilis - Yih-Gang Goan; Mingzi M. Zhang; Lun Kelvin Tsou; Zhi-Hong Wen; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; Yu-Jen Wu; Jih-Jung Chen; Hai Nhat Do; Pei-Luen Jiang; Ping-Jyun Sung (Phytochemistry Letters, 2025)

Enhancing the Fe3+/Fe2+ biocatalytic cycle using deoxidizing and iron-releasing sticks to improve bio-fenton efficiency - Chi-Wen Lin; Chung-Yen Yeh; Chih-Yu Ma; Shu-Hui Liu (Journal of Water Process Engineering, 2025)

Insights into algae cell inactivation by mixed chlor(am)ines in source water: Unraveling removal mechanisms, derived risks and control methods - Zhu Peng; Tian-Yang Zhang; Qi Fu; Xiang-Chi Xie; Zhen-Ning Luo; Yu-Lin Tang; Huan He; Chao Zeng; Jian Lu; Yun-Qiao Zeng; Chen-Yan Hu; Bin Xu (Journal of Environmental Chemical Engineering, 2025)

Small intestine-residing probiotics suppress neurotoxic bile acid production via extracellular vesicle-mediated inhibition of Clostridium scindens - Wei-Leng Chin; Bao-Hong Lee; Qiao-Yu Hsu; Chih-Yao Hou; Ming-Chyi Pai; Chi-Wei Lin; Wei-Hsuan Hsu (Food Research International, 2025)

Unravelling the response mechanism of extracellular polysaccharides synthesis and salt stress resistance in Tetragenococcus halophilus JY1biofilm formation - Jiayi Lin; Chi Zhao; Jvliang Dai; Yu Zhang; Fangming Lan; Lixin Luo (Food Bioscience, 2025)

Terpenoids with Antiangiogenic Activity from Formosan Soft Coral Caementabunda hypotentaculata - Hsin Huang; Chen-Yu Yang; Shih-Wei Wang; Limbadri Salendra; Shu-Rong Chen; Tzi-Yi Ke; Yu-Liang Yang; Yu-Chi Lin; Yuan-Bin Cheng (Marine Biotechnology, 2025)

Kirenol ameliorates endotoxin-induced acute lung injury by inhibiting the ERK and JNK phosphorylation–mediated NFκB pathway in mice - Frank Cheau-Feng Lin; Shih-Pin Chen; Sheng-Chien Lin; Ching-Chi Tseng; Stella Chin-Shaw Tsai; Yu-Hsiang Kuan (Inflammopharmacology, 2025)

Polyploid crape myrtle was produced through hybridizing with 2n gametes induced by high-temperature - Yu Xu; Qi Hu; Qifang Lin; Xiufeng Chi; Ping Shen; Xin Wang; Zhiting Wan; Xinwei Jiang; Jia Wang; Tangren Cheng; Qixiang Zhang; Huitang Pan (Euphytica, 2025)

What does it mean when the pleasant smells come and go? Correlation between UPSIT odor identification status and fluctuation of non-motor symptoms in Parkinson’s disease - Hsin-Bei Lei; Ting-Chun Fang; Yu-Hsuan Lin; Shih-Chi Chiu; Ming-Hong Chang; Yi-Jen Guo (Acta Neurologica Belgica, 2025)
Parkinson’s disease (PD) is characterized by motor and non-motor symptoms, including olfactory dysfunction. Prior studies have shown that olfaction deteriorates with disease progression, however fluctuations in olfaction and related PD symptoms have been less explored. This study aimed to investigate correlations between changes in odor identification ability and PD symptoms. PD patients recruited from Taichung Veterans General Hospital underwent at least two consecutive Movement Disorder Society Unified Parkinson’s Disease Rating Scale (MDS-UPDRS) and University of Pennsylvania Smell Identification Test (UPSIT) evaluations. The patients were grouped based on changes in olfactory identification ability between evaluations, and fluctuations in PD symptoms were compared between groups. Ninety-seven PD patients with 114 complete sets of data were analyzed. Significant divergent results were observed between changes in five MDS-UPDRS non-motor subscores and the conversion status of five pleasant odors, including anxiety vs. bubble gum, apathy vs. banana, dizziness vs. coconut, urination vs. root beer, and dopamine dysregulation syndrome (DDS) vs. grape. Fluctuations in the ability to detect pleasant odors, may have a complex interaction with other non-motor symptoms, including in the neurobehavioral and autonomic domains. Serial monitoring of olfactory function, particularly with pleasant odors, may provide valuable insights for tracking non-motor symptoms in PD and warrants further investigation into their therapeutic implications.

Unveiling secondary inorganic PM2.5 pollution in northern Taiwan: The role of aerosol acidity and transformation processes - Ankita Katoch; Chi-Chi Lin; Yu-Chieh Ting; Thi Phuong Thao Ho; Kuan-Ting Liu; Atar Singh Pipal; Yu-Hsiang Cheng (Science of The Total Environment, 2025)

Safety evaluation of Limosilactobacillus fermentum PS150 for use as a commercial psychobiotic - Li-Hao Cheng; Chien-Chen Wu; Chin-Lin Huang; Yu-Hsuan Wei; Pei-Jun Wen; Shih-Hau Chiu; Chien-Chi Chen; Ching-Ting Lin; Po-Lin Liao (Food and Chemical Toxicology, 2025)

Enhanced reaction kinetics of sterically hindered amines in semi-aqueous N-methyl-2-pyrrolidone for CO2 capture - Chi-Hui Cheng; Yu-Fan Chen; Yu-Jeng Lin (Chemical Engineering Journal, 2025)

An injectable in situ-forming hydrogel with self-activating genipin-chitosan (GpCS) cross-linking and an O2/Ca2+ self-supplying capability for wound healing and rapid hemostasis - Chi Lin; Tzu-Wei Lu; Fang-Yu Hsu; Tzu-Wen Huang; Ming-Hua Ho; Hsien-Tsung Lu; Fwu-Long Mi (Carbohydrate Polymers, 2025)

In vitro and in silico studies on α-glucosidase inhibitory properties of bioactive components from the rhizomes of Alpinia officinarum Hance - Zakhele Mphatsi Dlamini; Bongani Sicelo Dlamini; Shih-Han Fu; Ya-Lin Chang; Chi-Chien Lin; Yu-Kuo Chen; Kok-Tong Tan; Chi-I Chang (Medicinal Chemistry Research, 2025)

AI integration into wavelength-based SPR biosensing: Advancements in spectroscopic analysis and detection - Ying-Feng Chang; Yu-Chung Wang; Tsung-Yu Huang; Meng-Chi Li; Sin-You Chen; Yu-Xen Lin; Li-Chen Su; Kwei-Jay Lin (Analytica Chimica Acta, 2025)

Versatile g-C3N4/AlOOH nanocomposites: Efficient photocatalyst for dye removal, algae inactivation, and glucose detection - Hsiu-Cheng Chen; Ting-Yu Lin; Hsin-Cheng Peng; Yu-Hsuan Lee; Ruey-Chi Wang (Chemosphere, 2025)

Probabilistic mapping of imbalanced data for groundwater contamination using classification algorithms: Performance and reliability - Yang Qiu; Aiguo Zhou; Hanxiang Xiong; Defang Zhang; Cheng Su; Shizheng Zhou; Lin Go; Chi Yang; Hao Cui; Wei Fan; Yao Yu; Fawang Zhang; et al. (Groundwater for Sustainable Development, 2025)

Ambient stable ZnBr2-assisted lead-free perovskite for enhanced piezoelectricity of polyvinylidene fluoride in versatile piezo-phototronic applications - Manikandan Venkatesan; Wei-Chun Lin; Wei-Cheng Chen; Jayashree Chandrasekar; Yu-Hang Huang; Kai-Wei Lin; Zih-Syuan Syu; Ja-Hon Lin; Wei-Hung Chiang; Wei-Ren Liu; Ye Zhou; Chi-Ching Kuo (Chemical Engineering Journal, 2025)

Highly active Cu-embedded in magnetic carbon nanofibers for the reduction of 4-nitrophenol - Ching-Shiun Chen; Tse-Ching Chen; Kai-Lin Chiu; Cheng-Rong Hsing; Li-Yu Wang; Chia-Min Yang; Chih-Wen Pao; Chi-Liang Chen (Chemical Engineering Journal, 2025)

Thiol-linked hyaluronic acid-mediated encapsulation of RCR-stabilized gold nanoclusters for hyaluronidase sensing and cellular imaging - Manivannan Madhu; Meng-Yuan Tsai; Ming-Mu Hsieh; En-Yu Lin; Wei-Bin Tseng; Chi-Yu Lu; Wei-Lung Tseng (Carbohydrate Polymers, 2025)

Digital transformation of mental health therapy by integrating digitalized cognitive behavioral therapy and eye movement desensitization and reprocessing - Ju-Yu Wu; Ying-Ying Tsai; Yu-Jie Chen; Fan-Chi Hsiao; Ching-Han Hsu; Yen-Feng Lin; Lun-De Liao (Medical & Biological Engineering & Computing, 2025)

Role of MFN2 in bovine embryonic development and the mitigation of ER stress - Shu-Ming Shi; Bing Hu; Zhi-Chao Chi; Lin-Yi Qu; Li-Ying Liu; Yu-Yan He; Guan-Lin Jia; Jing-Hang Li; Ilkeun Kong; Yong-Xun Jin; Xian-Feng Yu (Animal Reproduction Science, 2025)

Enhancing indoor air quality and cardiopulmonary health in patients with asthma by photocatalytic oxidation and filters air cleaner - Jia Lin Zhang; Guan-Yu Liao; Hong-Yi Lin; Jie-An Xie; Wan-Chen Li; Huang-Chi Chen; Da Wei Wu; Huai-Lei Juan; Jia-Yu Kuo; Pei-Shih Chen (Journal of Hazardous Materials, 2025)

Antimicrobial efficacy of carvacrol-loaded curdlan hydrogels for enhancing shelf-life in seafood packaging applications - Hong-Ting Victor Lin; Yi-Chi Yu; Shu-Han Yu; Yu-Chieh Chou; Hsuan-Ju Lin; Shella Permatasari Santoso; Shin-Ping Lin (International Journal of Food Microbiology, 2025)

Dual functionality of carbazole-based phosphonic acid molecular additives realizes efficient hole transport layer-free perovskite light-emitting diodes - Yin-Ti Lai; Chiung-Han Chen; Ming-Hsuan Yu; Hsing-Yu Kuo; I-Chih Ni; Bi-Hsuan Lin; Hobeom Kim; Chi-Ching Kuo; Yu-Jung Lu; Chu-Chen Chueh (Chemical Engineering Journal, 2025)

Determinants of soundscape quality of communal open space in Hong Kong - Minqi LIN; Chi Kwan CHAU; Shiu Keung TANG; Wai Kit CHUNG; Ho Man YU (Building and Environment, 2025)

The obesity-related mutation gene on nonalcoholic fatty liver disease - Yen-Yu Chen; Chi-Sheng Chen; Jee-Fu Huang; Wen-Hsiu Su; Chia-Yang Li; Wei-Shiun Chen; En-Sheng Lin; Wan-Long Chuang; Ming-Lung Yu; Shu-Chi Wang (Human Genetics, 2025)

Quantifying the effects of the microphysical hygroscopic restructuring of soot on ensemble optical properties and satellite aerosol optical depth retrievals - Kuo-En Chang; Tang-Huang Lin; Ta-Chih Hsiao; Yi-Ling Chang; Tzu-Chi Lin; Chih-Yu Chan; Charles C.-K. Chou (Science of The Total Environment, 2024)

Long-term subculture induces syncytialization and influent the response to bisphenol A (BPA) of placental JEG-3 cells - Yu-Shiuan Huang; Ai-An Chang; Zhi-Jie Yang; Jung-An Chen; Chi-Kang Lin; Hsin-Chieh Lan (Reproductive Toxicology, 2024)

Identification of BpEXP family genes and functional characterization of the BpEXPA1 gene in the stems development of Betula platyphylla - Yao Chi; Zihan Wang; Shizhong Chen; Lin Feng; Meiqi Zhou; Yang Li; Ying Yu; Caiqiu Gao; Chao Wang (Journal of Plant Physiology, 2024)

Plasmonic Au-NPs photodecorated on NiCoLDH nanosheets as a flexible SERS sensor for the real-time detection of fipronil - Nazar Riswana Barveen; Sathishkumar Chinnapaiyan; Che-Wei Zeng; Chi-Hsien Huang; Yen-Yu Lin; Yu-Wei Cheng (Journal of Hazardous Materials, 2024)

Bio-inspired sustainable electrospun quantum nanostructures for high quality factor enabled face masks and self-powered intelligent theranostics - Loganathan Veeramuthu; Ren-Jie Weng; Wei-Hung Chiang; Archana Pandiyan; Fu-Jie Liu; Fang-Cheng Liang; G. Ranjith Kumar; Hua-Yi Hsu; Yu-Ci Chen; Wen-Yinn Lin; Yao-Chun Tang; Wan-Rong Lin; et al. (Chemical Engineering Journal, 2024)

From agricultural biomass to D form lactic acid in ton scale via strain engineering of Lactiplantibacillus pentosus - Chia-Chi Yang; Chia-Hau Chou; Gia-Luen Guo; Yu-Ju Lin; Fu-Shan Wen (Bioresource Technology, 2024)

The association of air pollution with blood pressure, heart rate and stress among office workers using essential oils - Chien-Yu Lee; I-Jung Liu; Chih-Hong Pan; Lian-Yu Lin; Hsiao-Chi Chuang; Kin-Fai Ho; Chia-Huang Chang; Kai-Jen Chuang (Atmospheric Environment, 2024)

Preparation and Characterization of a Novel Ca-Fe-Si-S Composite for the Simultaneous Stabilization of Heavy Metals in Arsenic Slag - Ge Zhang; Huifen Yang; Xingjie Lin; Yu Miao; Chi Zhang; Fangze Li; Zhikun Pang; Xin Xin (Water, Air, & Soil Pollution, 2024)

SLC10A1 rs2296651 variant (S267F mutation) predicts biochemical traits, hepatitis B virus infection susceptibility and the risk of gallstone disease - Yu-Lin Ko; Wei-Lun Tuan; Ming-Sheng Teng; Wei-Chih Su; Chia‑Chi Wang; Leay-Kiaw Er; Semon Wu; Lung-An Hsu (Molecular Genetics and Genomics, 2024)

Targeting PADI2 as a potential therapeutic strategy against metastasis in oral cancer via suppressing EMT-mediated migration and invasion and CCL3/5-induced angiogenesis - Shih-Kai Hung; Chih-Chia Yu; Hon-Yi Lin; Wen-Yen Chiou; Moon-Sing Lee; Ru-Inn Lin; Ming-Chi Lu (Clinical & Experimental Metastasis, 2024)

Toxicity, mutagenicity, and source identification of polycyclic aromatic hydrocarbons in ambient atmosphere and flue gas - Shih Yu Pan; Ya Syuan Wu; Yu-Cheng Chen; Yen-Shun Hsu; Yu Chi Lin; Pao Chen Hung; Charles C.-K. Chou; Somporn Chantara; Yuan Cheng Hsu; Kai Hsien Chi (Environmental Science and Pollution Research, 2024)
This study aimed to assess the characteristics of particulate matter (PM) and polycyclic aromatic hydrocarbons (PAHs) from various stationary and mobile emission sources in Taiwan, with a focus on source apportionment and associated health risks. The northern power plant, equipped with bag filters operating at 150 °C, had significantly lower FPM and CPM levels (0.44 and 0.13 mg/m 3 , respectively) compared to the central and southern power plants, which used electrostatic precipitators operating at 250 °C (FPM, 1.45–8.35 mg/m 3 ; CPM, 2.37–3.73 mg/m 3 ). Additionally, emissions from diesel vehicles under both idle and high-speed conditions exhibited higher FPM levels (3.46–4.67 mg/m 3 ) than gasoline vehicles (0.19–0.40 mg/m 3 ). In terms of PAH toxicity, diesel vehicle emissions had significantly higher BaP-TEQ (87.3 ng/m 3 ) and BaP-MEQ (25.9 ng/m 3 ) levels compared to power plants (BaP-TEQ, 5.49 ng/m 3 ; BaP-MEQ, 2.65 ng/m 3 ). The highest ambient concentrations of PM2.5, BaP-TEQ, and BaP-MEQ were recorded at traffic sites, with values of 48 ± 36 µg/m 3 , 0.29 ng/m 3 , and 0.11 ng/m 3 , respectively. Differences in PAH distributions between stationary and mobile sources were influenced by factors such as pollution control technologies, combustion temperatures, and fuel types. Diesel vehicle emissions were dominated by benzo[g,h,i]perylene (BghiP), indeno[1,2,3-cd]pyrene (IND), benzo[a]pyrene (BaP), and benzo[b]fluoranthene (BbF) under idle conditions, while phenanthrene (PA), pyrene (Pyr), and BghiP were prevalent under high-speed conditions. Source apportionment conducted using principal component analysis (PCA) and positive matrix factorization (PMF) identified diesel and gasoline vehicles as the dominant contributors to atmospheric PAHs in Taiwan, accounting for 38% of the total, followed by coal-fired power plants at 35%. The highest lifetime excess cancer risk (ECR) of 2.5 × 10⁻ 5 was observed in traffic-dense areas, emphasizing the public health implications of vehicle emissions. The study adds credibility to the source apportionment findings, and the health risk analysis highlights variations across different regions, including traffic, urban, rural, and background zones.

Investigating illicit drug hotspots and daily variations using sewer-network wastewater analysis - Hank Hui-Hsiang Lin; Ming-Chi Hsieh; Jennifer Ia Wen Wen Liu; Yu-Hsiang Wang; Shu-Jie Huang; En Lien; Li-Wei Huang; Pei-Te Chiueh; Hsin-Hsin Tung; Angela Yu-Chen Lin (Chemosphere, 2024)

Performance and biotoxicity of electro-Fenton treatment of bisphenol A: Evaluation of copper recovered from microbial fuel cell cathodes for subsequent catalytic applications - Chi-Wen Lin; Guan-Yi Chen; Shu-Hui Liu; Wei Tong Chen; Shih-Hsien Chang; Chih-Yu Ma (Process Safety and Environmental Protection, 2024)

Phylogenetic relationships and historical biogeography of silkmoths (Lepidoptera: Bombycidae) suggest an origin in Southern Gondwana - Rung-Juen Lin; Yu-Chi Lin; Michael F. Braby; Andreas Zwick; Yu-Feng Hsu (Molecular Phylogenetics and Evolution, 2024)

Effects of physical sterilization on microbial safety, nutritional composition, and antioxidant activity of queen bee larva powder, a by-product of royal jelly production - Yu-Hsin Chen; Jer-An Lin; Chi-Chung Peng; Pei-Shou Hsu; Tzu-Hsien Wu; Yen-Hou Chen; Ming-Cheng Wu (Food Control, 2024)

Facile coupling of plasmonic Au-NPs on ZnS NFs as a robust SERS substrate for toluidine blue detection and degradation - Nazar Riswana Barveen; Sathishkumar Chinnapaiyan; Chi-Hsien Huang; Yen-Yu Lin; Jia-Lun Xu; Yu-Wei Cheng (Analytica Chimica Acta, 2024)

Important contributions of natural gas combustion to atmospheric nitrate aerosols in China: Insights from stable nitrogen isotopes - Yu-Chi Lin; Mei-Yi Fan; Yihang Hong; Mingyuan Yu; Fang Cao; Yan-Lin Zhang (Science Bulletin, 2024)

Combined effects of thermal environment and gene regulation on metabolic enzyme activities of major metabolic tissues in a winter-breeding amphibian - Chi-Ying Zhang; Hua-Li Hu; Yu Wang; Lin Zhang; Guo-Hua Ding (Journal of Thermal Biology, 2024)

Achieving over 42 % indoor efficiency in wide-bandgap perovskite solar cells through optimized interfacial passivation and carrier transport - Zhong-En Shi; Ta-Hung Cheng; Chien-Yu Lung; Chi-Wei Lin; Chih-Lin Wang; Bing-Huang Jiang; Yu-Sheng Hsiao; Chih-Ping Chen (Chemical Engineering Journal, 2024)

Regulating iron center by defective MoS2 for superior Fenton-like catalysis in water purification: The key role of surface interaction and superoxide radical in accelerating metal redox-cycling - Ai-Yong Zhang; Zhi-Xian Lin; Jing-Yu Zhang; Ming-He Zhang; Chi Zhang; Lu Zhao; Liang Liu; Wei Da; Lyumeng Ye (Chemosphere, 2024)

Dynamic migration and risk of cephalosporin antibiotic resistance genes: Move from pharmaceutical plants through wastewater treatment plants to coastal tidal flats sediments - Chifei Dong; Zishu Liu; Lin Zhu; Baofeng Zhang; Taolve Chi; Zhendi Yu; Meng Zhou; Lingtao Sun; Yuxiang Zhao; Lizhong Zhu; Baolan Hu (Water Research, 2024)

The impact of flooding from the Minjiang River on the succession of harmful algal blooms (HABs) caused by diatoms in China's offshore waters - Yun-Chi Lin; Ya-Han Nien; Kuo-Ping Chiang; Chien-Pang Chin; Wei-Ting Chen; Gwo-Ching Gong; Wen-Chen Chou; Chi-Yu Shih; Kuo-Shu Chen (Marine Pollution Bulletin, 2024)

Organic light-emitting diode therapy promotes longevity through the upregulation of SIRT1 in senescence-accelerated mouse prone 8 mice - Yue-Hua Deng; Chi-Sheng Chiou; Ching-Yu Tsai; Abhinay Kumar Singh; Edlin Anahi Pelaze Achtmann; Bou-Yue Peng; Tommy Yet-Min Lin; Hsin-Chung Cheng; Pao-Chang Chiang; Win-Ping Deng (Journal of Photochemistry and Photobiology B: Biology, 2024)

Dual-Targeting EGCG/NO-Supplying protein assembled nanoparticles with Multi-Synergistic effects against atherosclerosis - Chi Lin; Tsai-Mu Cheng; Yun-Chun Liu; Fang-Yu Hsu; Chun-Ming Shih; Min-Lang Tsai; Chun-Che Shih; Fwu-Long Mi (Chemical Engineering Journal, 2024)

TBC1D10B promotes tumor progression in colon cancer via PAK4‑mediated promotion of the PI3K/AKT/mTOR pathway - Xiao-Jv Chi; Yi-Bei Song; Haoran Zhang; Li-Qiang Wei; Yong Gao; Xue-Jing Miao; Shu-Ting Yang; Chun-Yu Lin; Dong Lan; Xiquan Zhang (Apoptosis, 2024)

Kaguacidine A: a novel spirohydantoin-containing cucurbitane glycoside from vines of Momordica charantia L. - Hung-Tse Huang; I-Wen Lo; Yu-Chi Lin; Liao Geng-You; Yun-Sheng Lin; Li-Jie Zhang; Tsung-Lin Li; Chia-Ching Liaw; Yao-Haur Kuo (Natural Product Research, 2024)

Evaluation of spatial and temporal changes in illicit drug use in the Taipei metropolitan area via wastewater-based epidemiology - Hank Hui-Hsiang Lin; Yu-Hsiang Wang; Jennifer Ia Wen Wen Liu; Ming-Chi Hsieh; Shu-Jie Huang; En Lien; Li-Wei Huang; Angela Yu-Chen Lin (Science of The Total Environment, 2024)

Sulfur dioxide-triggered visualization tool for auxiliary diagnosis of alcohol-induced “anti-inflammatory and pro-inflammatory” development process - Jiangfeng Li; Hanwen Chi; Yu Wu; Kanghui Peng; Jiangyan Wang; Weiying Lin (Journal of Hazardous Materials, 2024)

Impact of metformin on neocortical development during pregnancy: Involvement of ERK and p35/CDK5 pathways - Muhammet Oner; Mei-Chih Chen; Pang-Ting Cheng; Yu-Hsuan Li; Yu-Chiao Cheng; Ayse Celik; Shiuan-Woei Soong; Li-Wen Hsu; Din-You Lin; G.M. Shazzad Hossain Prince; Trayee Dhar; Hsu-Chen Cheng; et al. (Chemosphere, 2024)

Sunlight enhanced the formation of tribromomethane from benzotriazole degradation during the sunlight/free chlorine treatment in the presence of bromide - Ming-Chi Hsieh; Wan-Ning Lee; Yi-Hsuan Chu; Hank Hui-Hsiang Lin; Angela Yu-Chen Lin (Chemosphere, 2024)

Isolation of 24-homoscalarane sesterterpenoids from a sponge of the genus Lendenfeldia - Li-Guo Zheng; You-Yan Chen; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; Yi-Hao Lo; Yu-Chi Tsai; Hao-Chun Hu; You-Ying Chen; Tsong-Long Hwang; Tzu-Ming Ou; Ping-Jyun Sung (Phytochemistry Letters, 2024)

Enzymatic impregnation by high hydrostatic pressure for preparing shape-retaining softened broccoli and carrot - Yu-Hsiang Wu; Bo-Chi Huang; Yan-Han Lin; Chung-Yi Wang (Food Bioscience, 2024)

Study of a commercial-scale poultry manure oxy-fuel gasification plant via CFD modeling and safety assessment - Qinwen Liu; Yiying Wang; Wei Quan Leong; Yonghua Gu; Alexander Lin; Yuchen Wang; Aibing Yu; Wenqi Zhong; Chi-Hwa Wang (Biomass and Bioenergy, 2024)

Losing Tidal Flats at the Midpoint of the East Asian-Australasian Flyway over the past 100 Years - Wan-Jyun Chen; An-Yu Chang; Chia-Chi Lin; Ruey-Shing Lin; Da-Li Lin; Pei-Fen Lee (Wetlands, 2024)
The ecosystem services and functions of tidal flats have been overlooked for many decades, and tidal flat loss has been identified as a serious threat to many taxa in recent years, especially for migratory waterbirds. Despite the understanding of tidal flats change on the global scale, there are still a lot of unknowns on the small scale, including tidal flats in Taiwan, which are important stopover sites for migratory waterbirds along the East Asian–Australasian Flyway. Therefore, we collated historic topographic maps, Landsat Archive images between the 1920s and the 2020s to determine the trajectories of tidal flat change along the coastline of Taiwan. Our results show that tidal flat coverage expanded between the 1920s and the 1950s, but lost approximately 266 km 2 (58%) between the 1950s and the 2010s. The status of the tidal flats along the western coastline of Taiwan has been identified as “Endangered” based on the criteria of the IUCN Red List of Ecosystems. According to the aims of the Global Biodiversity Framework, we suggest rethinking the land use plans along the coastline to mitigate the tidal flat loss, especially the controversial issues concerning the expansion of green energy infrastructure. To realize the Nature Positive goals by 2030, recovering and restoring the tidal flat ecosystem could be one of the key strategies.

Examining arterial pulsation to identify and risk-stratify heart failure subjects with deep neural network - Chieh-Chun Huang; Shih-Hsien Sung; Wei-Ting Wang; Yin-Yuan Su; Chi-Jung Huang; Tzu-Yu Chu; Shao-Yuan Chuang; Chern-En Chiang; Chen-Huan Chen; Chen-Ching Lin; Hao-Min Cheng (Physical and Engineering Sciences in Medicine, 2024)
Hemodynamic parameters derived from pulse wave analysis have been shown to predict long-term outcomes in patients with heart failure (HF). Here we aimed to develop a deep-learning based algorithm that incorporates pressure waveforms for the identification and risk stratification of patients with HF. The first study, with a case–control study design to address data imbalance issue, included 431 subjects with HF exhibiting typical symptoms and 1545 control participants with no history of HF (non-HF). Carotid pressure waveforms were obtained from all the participants using applanation tonometry. The HF score, representing the probability of HF, was derived from a one-dimensional deep neural network (DNN) model trained with characteristics of the normalized carotid pressure waveform. In the second study of HF patients, we constructed a Cox regression model with 83 candidate clinical variables along with the HF score to predict the risk of all-cause mortality along with rehospitalization. To identify subjects using the HF score, the sensitivity, specificity, accuracy, F1 score, and area under receiver operating characteristic curve were 0.867, 0.851, 0.874, 0.878, and 0.93, respectively, from the hold-out cross-validation of the DNN, which was better than other machine learning models, including logistic regression, support vector machine, and random forest. With a median follow-up of 5.8 years, the multivariable Cox model using the HF score and other clinical variables outperformed the other HF risk prediction models with concordance index of 0.71, in which only the HF score and five clinical variables were independent significant predictors (p < 0.05), including age, history of percutaneous coronary intervention, concentration of sodium in the emergency room, N -terminal pro-brain natriuretic peptide, and hemoglobin. Our study demonstrated the diagnostic and prognostic utility of arterial waveforms in subjects with HF using a DNN model. Pulse wave contains valuable information that can benefit the clinical care of patients with HF.

Numerical seismic performance assessment and fragility analysis for gravity-type wharves considering the influence of soil liquefaction - Yung-Yen Ko; Ho-Hsiung Yang; Chi-Wen Hu; Yan-Jhih Huang; Yu-Ying Lin (Soil Dynamics and Earthquake Engineering, 2024)

Backward and forward simulation of polycyclic aromatic hydrocarbons by the grid-scale model _validation and applications for environmental management - Ming-Tsuen Hsieh; Wen-Yu Chung; Shoiw-Mei Tseng; Pei-Chi Shih; Shau-Ku Huang; Chon-Lin Lee (Atmospheric Environment, 2024)

Nucleocytoplasmic shuttling of BEFV M protein-modulated by lamin A/C and chromosome maintenance region 1 through a transcription-, carrier- and energy-dependent pathway - Yu-Kang Chang; Yi-Jyum Lin; Ching-Yuan Cheng; Pei-Chien Tsai; Chi-Young Wang; Brent L. Nielsen; Hung-Jen Liu (Veterinary Microbiology, 2024)

Morphology and chemical composition of Taiwan oil millet (Eccoilopus formosanus) epicuticular wax - Marita Anggarani; Yu-Ying Lin; Shao-An Fang; Hshin-Ping Wu; Chi-Chih Wu; Wann-Neng Jane; Thomas James Roscoe; Frederic Domergue; Yue-Ie Caroline Hsing (Planta, 2024)

Wet peroxide oxidation process catalyzed by Cu/Al2O3: phenol degradation and Cu2+ dissolution behavior - Wumin Zhang; Huimin Zhuang; Yu Guo; Hua Chi; Qiuyue Ding; Lu Wang; Yanyan Xi; Xufeng Lin (Environmental Science and Pollution Research, 2024)

Impact of occupational noise exposure on the hearing level in hospital staffs: a longitudinal study - Tang-Chuan Wang; You-Cheng Yu; Alan Hsu; Jia-Yi Lin; Yung-An Tsou; Chiu-Shong Liu; Kai-Jen Chuang; Wen-Chi Pan; Chin-An Yang; Sung-Lin Hu; Chien-Yi Ho; Tzu-Liang Chen; et al. (Environmental Science and Pollution Research, 2024)

Mirror QCD phase transition as the origin of the nanohertz Stochastic Gravitational-Wave Background - Lei Zu; Chi Zhang; Yao-Yu Li; Yuchao Gu; Yue-Lin Sming Tsai; Yi-Zhong Fan (Science Bulletin, 2024)

Perturbation of lipid metabolism in 3T3-L1 at different stages of preadipocyte differentiation and new insights into the association between changed metabolites and adipogenesis promoted by TBBPA or TBBPS - Yun-Jiang Yu; Jing-Lin Tian; Tong Zheng; Hong-Xuan Kuang; Zong-Rui Li; Chao-Jie Hao; Ming-Deng Xiang; Zhen-Chi Li (Journal of Hazardous Materials, 2024)

Experimental verification of seismic vibration control of high-rise buildings with friction-type multiple tuned mass dampers - Ging-Long Lin; Chi-Chang Lin; Tsung-Han Yang; Hao-Yu Lung (Engineering Structures, 2024)

Efficient and cost-effective method for identifying urban ventilation corridors using a heuristic search algorithm - Tsz-Kin Lau; Pei-Chi Tsai; Hsing-Yu Ou; Tzu-Ping Lin (Sustainable Cities and Society, 2024)

Assessment of sources and health risks of heavy metals in metropolitan household dust among preschool children: The LEAPP-HIT study - Chi-Sian Kao; Ying-Lin Wang; Chuen-Bin Jiang; Pei-Ju Tai; Yi-Hua Chen; Hsing-Jasmine Chao; Yu-Chun Lo; Zeng-Yei Hseu; Hsing-Cheng Hsi; Ling-Chu Chien (Journal of Environmental Management, 2024)

Effect of stress on the rehabilitation performance of rats with repetitive mild fluid percussion-induced traumatic brain injuries - Yu-Lin Wang; Chi-Chun Chen; Ching-Ping Chang (Cognitive Neurodynamics, 2024)

Exploring the potential of the nano-based sunscreens and antioxidants for preventing and treating skin photoaging - Chih-Hung Lin; Ming-Hsien Lin; Yu-Kuo Chung; Ahmed Alalaiwe; Chi-Feng Hung; Jia-You Fang (Chemosphere, 2024)

The application of strategy based on LSTM for the short-term prediction of PM2.5 in city - Min-Der Lin; Ping-Yu Liu; Chi-Wei Huang; Yu-Hao Lin (Science of The Total Environment, 2024)

Molecular compositions of marine organic aerosols over the Bohai and Yellow Seas: Influence of primary emission and secondary formation - Fang Cao; Yi-Xuan Zhang; Yan-Lin Zhang; Wen-Huai Song; Yu-Xian Zhang; Yu-Chi Lin; Chaman Gul; Md. Mozammel Haque (Atmospheric Research, 2024)

Impact of Pacific–Japan pattern on temperature and heatwave events in summer over Taiwan - Wan‐Ling Tseng; Szu‐Ying Lin; Yi‐Chi Wang; Shih‐How Lo; Min‐Hui Lo; Shih‐Yu Lee; Chieh‐Ting Tsai; Huang‐Hsiung Hsu (International Journal of Climatology, 2023)
The prediction of heatwave events is vital to provide information on possible hazards caused by extremely high temperature. The Pacific–Japan (PJ) pattern is a significant climate variability that controls the summer climate over East Asia. Previous studies have reported that the meridional propagating wave structure associated with the PJ pattern can modulate summer temperature and heatwave characteristics over northeast Asian countries, such as Korea and Japan. Nevertheless, its impacts on the subtropical regions, including Taiwan, a mountainous subtropical island with an approximate population of 24 million, is not yet fully understood. In this study, we investigate the impacts of the PJ pattern on the summer temperature and heatwave characteristics in Taiwan on the interannual timescale using long‐term station‐based temperature and rainfall dataset. We found an island‐wide increase in temperature during the positive phase of the PJ pattern, which is characterized by an anticyclonic anomalous circulation over Taiwan. Meanwhile, the averaged effective area and frequency of heatwave extremes over Taiwan have increased significantly, indicating an increase of exposure to heatwaves. Our examinations of large‐scale environment suggest that the adiabatic warming due to subsidence anomaly associated with the anticyclone over Taiwan is primary contributor of surface warming, which is balanced by diabatic cooling and meridional advective cooling on a seasonal timescale. Our study consolidated the links between the PJ pattern as a climate driver, hot summers and increased summer heatwave events over Taiwan. By combining with the seasonal prediction systems and early warning systems, such understanding can help sectors that are vulnerable to heat stress to prepare for potential hazards.

Evaluating the toxic mechanism of 1,2-diacetylbenzene in neural cells/tissues: The favorable impact of silibinin - Li-Yu Fay; Jun-Yi Chien; Ching-Feng Weng; Huai-Sheng Kuo; Dann-Ying Liou; Wei-Hao Weng; Chi-Hung Lin; Ya-Tzu Chen; Wen-Hung Huang; Wen-Cheng Huang; May-Jywan Tsai; Henrich Cheng (NeuroToxicology, 2023)

Enhanced biodegradation kinetics in the copper-polluted sediment through bioaugmentation with water spinach and peanut husk-derived biochar - Lidia Kristia Alfanti; Chih-Yu Ma; Chi-Wen Lin (Journal of Water Process Engineering, 2023)

A crosslinked waterborne poly(vinyl acetate) for greenhouse gas fixation with improved elastomeric properties, shape-memory ability, and recyclability - Yen-Chuan Chen; Ying-Chi Huang; Yi-Hua Huang; Ying-Feng Lin; Ho-Ching Huang; Ru-Jong Jeng; Yu-Wei Cheng; Chien-Hsin Wu (Journal of Environmental Chemical Engineering, 2023)

Comparison of high-hydrostatic pressure and frozen treatments on raw freshwater clam marinated in soy sauce: Impact on microbiological and organoleptic qualities - Pi-Chen Wei; Yi-Chen Lee; Yu-Chi Chen; Chung-Saint Lin; Po-Wei Chen; Todd Hsu; Yung-Hsiang Tsai (Food Control, 2023)

Evaluating the performance of particle oxidation catalyst for construction equipment - Aulia Nur Mustaqiman; John Paul Santos; Chen-Yu Lin; Fefi Eka Wardiani; Lin-Chi Wang (Atmospheric Pollution Research, 2023)

IoT-interfaced solid-contact ion-selective electrodes for cyber-monitoring of element- specific nutrient information in hydroponics - Yi-Min Wu; Shao-Yuan Liu; Bo-You Shi; Jui-Yu Peng; Zhi-Wei Kao; Yi-Yi Chen; Ting-Yu Hsieh; Hsing-Ying Chung; Chi-Yi Lin; Wei Fang; Lin-Chi Chen (Computers and Electronics in Agriculture, 2023)

Effectiveness and safety of botulinum neurotoxin for treating dyssynergic defecation: A systematic review and meta-analysis - Ching-Yu Chu; Yu-Chi Su; Pei-Chun Hsieh; Yu-Ching Lin (Toxicon, 2023)

Stochastic optimal control of mesostructure of supramolecular assemblies using dissipative particle dynamics and dynamic programming with experimental validation - Silabrata Pahari; Yu-Ting Lin; Shuhao Liu; Chi Ho Lee; Mustafa Akbulut; Joseph Sang-Il Kwon (Chemical Engineering Journal, 2023)

Associations between parental and postnatal metal mixture exposure and developmental delays in a Taiwanese longitudinal birth cohort of preschool children - Chi-Sian Kao; Yen-Tzu Fan; Ying-Lin Wang; Yi-Hua Chen; Hsing-Jasmine Chao; Yu-Chun Lo; Chuen-Bin Jiang; Ling-Chu Chien (Environmental Science and Pollution Research, 2023)

Inoculation of sulfate-reducing bacteria with a microbial fuel cell to treat groundwater that contains sulfolane: Improving performance, by-products and a biotoxicity assessment - Chi-Wen Lin; Yen-Hua Tseng; Chih-Yu Ma; Shu-Hui Liu (Journal of Water Process Engineering, 2023)

Exposure to incense burning, biomarkers, and the physical health of temple workers in Taiwan - Su-Er Guo; Pamela A. Ratner; Sung-Chih Tseng; Chieh-Mo Lin; Miao-Ching Chi; Chiang-Wen Lee; Ying-Chun Yu (Environmental Science and Pollution Research, 2023)
Incense burning releases heavy particulate matter (PM) and nitrogen dioxide (NO 2 ), known to have adverse effects on human health. Long-term exposure to PM and NO 2 increases inflammatory cytokine levels and can induce respiratory diseases. This study examined the association between incense burning exposure and the health status, especially inflammatory biomarkers, of temple workers and volunteers in Taiwan. The longitudinal observational study compared adult temple workers and volunteers, with long-term incense burning exposure, to residents from outpatient clinics in the Chiayi area. Forced expiratory volume in 1 s (FEV1) and serum and exhaled breath condensate (EBC) cytokines were assessed. Nonparametric Mann-Whitney U tests were used to compare cytokine levels of the exposure and control groups during the cold and hot weather seasons. FEV1 was significantly more diminished in the exposed group than in the control group during the cold season. Exposure status was associated with greater hot-cold seasonal differences in serum interleukins (IL)-1β (regression coefficient ( B ) = 6.6, 95% confidence interval (CI) = 5.0 to 8.3, p < .001), IL17-A ( B = 2.4, 95% CI = 0.3 to 4.5, p = .03), and plasminogen activator inhibitor [PAI]-1 ( B = 5.4, 95% CI = 1.5 to 9.3, p = .009). After adjusting for confounders, the groups’ serum levels of IL-1β, IL-17A, and PAI-1 significantly differed. EBC cytokines did not show significant differences. Elevated levels of IL-1β, IL17-A, and PAI-1 have been associated with various autoinflammatory syndromes and diseases. Given the cultural significance of incense burning, culturally sensitive interventions, including education, policy development, and program implementation, are crucial to protect individuals’ health, especially temple workers, from the adverse effects of exposure, addressing the manufacture, importation, and sale of incense.

Increased styrene vapor removal and power production by adding silicone oil to microbial fuel cell-based trickling filter - Wen-Hua Lin; Shu-Hui Liu; Chih-Yu Ma; Chi-Wen Lin (Process Safety and Environmental Protection, 2023)

Estimating the daily average concentration variations of PCDD/Fs in Taiwan using a novel Geo-AI based ensemble mixed spatial model - Chin-Yu Hsu; Tien-Wei Lin; Jennieveive B. Babaan; Aji Kusumaning Asri; Pei-Yi Wong; Kai-Hsien Chi; Tuan Hung Ngo; Yu-Hsuan Yang; Wen-Chi Pan; Chih-Da Wu (Journal of Hazardous Materials, 2023)

Sequential deacetylation/self-gelling chitin hydrogels and scaffolds functionalized with fucoidan for enhanced BMP-2 loading and sustained release - Hsien-Tsung Lu; Chi Lin; Yi-Ju Wang; Fang-Yu Hsu; Ju-Ting Hsu; Min-Lang Tsai; Fwu-Long Mi (Carbohydrate Polymers, 2023)

SWD1 epigenetically chords fungal morphogenesis, aflatoxin biosynthesis, metabolism, and virulence of Aspergillus flavus - Xiaohua Pan; Ling Hao; Chi Yang; Hong Lin; Dandan Wu; Xuan Chen; Mengjuan Zhang; Dongmei Ma; Yu Wang; Wangzhuo Fu; Yanfang Yao; Shihua Wang; et al. (Journal of Hazardous Materials, 2023)

New ent -kaurene and germacrene derivatives from Mesona procumbens Hemseley and their biological activity - Jerome G. Ganzon; Chia-Ching Liaw; Yu-Chi Lin; Zhi-Hu Lin; Chang-Hung Wang; Che-Yi Chen; Kuo-Hsiang Chuang; Yao-Haur Kuo (Natural Product Research, 2023)

Estimating arsenic biotransfer factors from feed to chicken: a viable approach to animal feed risk assessment - Ching-Chi Hung; Hsin-Tang Lin; Ching-Yi Chen; Kuan-Yi Chen; Tsung-Yu Lee; Chow-Feng Chiang (Food Additives & Contaminants: Part A, 2023)

Geological controls on the distribution of gas hydrates in the shallow parts of the gas hydrate stability zone – constraints from seafloor drilling off Taiwan - G. Bohrmann; C. Berndt; S. Lin; T.-H. Tu; A.T. Lin; H.-H. Hsu; M.-C. Lai; W.-C. Chi; C. Deusner; J. Elger; K. Wallmann; T. Freudenthal; et al. (Marine and Petroleum Geology, 2023)

Evaluation of alternative processes of methanol production from CO2: Design, optimization, control, techno-economic, and environmental analysis - Hsuan-Han Chiou; Chi-Jui Lee; Bo-Sheng Wen; Jian-Xun Lin; Cheng-Liang Chen; Bor-Yih Yu (Fuel, 2023)

Embryonic thermosensitivity and hatchling morphology differ among three species of crocodilians farm-raised in China - Dan Liu; Jia-Tian Chen; Jung-Chien Tsai; Cheng-Wang Li; Chi-Xian Lin; Yan-Fu Qu; Yu Du; Xiang Ji (Aquaculture, 2023)

Comparative analysis of the skin microbiota between two sea snakes, Hydrophis cyanocinctus and Hydrophis curtus, with versus without skin ulcer - Jun Zhong; Kun Guo; Zheng-Lan Liao; Yu Du; Chi-Xian Lin; Xiang Ji (Coral Reefs, 2023)

p-y based approach to predicting the response of monopile embedded in soft clay under long-term cyclic loading - Chi-Chin Tsai; Yu-Pai Li; Sheng-Hui Lin (Ocean Engineering, 2023)

Cardiac-specific overexpression of insulin-like growth factor II receptor-α interferes with the regulation of calcium homeostasis in the heart under hyperglycemic conditions - Shang-Yeh Lu; Bruce Chi-Kang Tsai; Dao Van Thao; Chin-Hu Lai; Michael Yu-Chih Chen; Wei-Wen Kuo; Chia-Hua Kuo; Kuan-Ho Lin; Dennis Jine-Yuan Hsieh; Chih-Yang Huang (Molecular Biology Reports, 2023)

Rab7a-mTORC1 signaling-mediated cholesterol trafficking from the lysosome to mitochondria ameliorates hepatic lipotoxicity induced by aflatoxin B1 exposure - Jin-Xian Lin; Chi-Yu Xu; Xin-Mou Wu; Lin Che; Ting-Yu Li; Su-Min Mo; Dong-Bei Guo; Zhong-Ning Lin; Yu-Chun Lin (Chemosphere, 2023)

Effects of biodegradation, biotoxicity and microbial community on biostimulation of sulfolane - Shao-Heng Chang; Chi-Wen Lin; Yu-Shen Cheng; Shu-Hui Liu (Chemosphere, 2023)

Effect of nanoclay supported nanosilver on the growth inhibition of aquatic pathogens and immunomodulatory effect in Penaeus vannamei - Zhen-Hao Liao; Huai-Ting Huang; Yu-Ru Lin; Chi-Yun Hu; Yu-Hsuan Kai; Jiang-Jen Lin; Fan-Hua Nan (Fish & Shellfish Immunology, 2023)

PanGu Drug Model: learn a molecule like a human - Xinyuan Lin; Chi Xu; Zhaoping Xiong; Xinfeng Zhang; Ningxi Ni; Bolin Ni; Jianlong Chang; Ruiqing Pan; Zidong Wang; Fan Yu; Qi Tian; Hualiang Jiang; et al. (Science China Life Sciences, 2023)

α7 nicotinic acetylcholine receptor agonist improved brain injury and impaired glucose metabolism in a rat model of ischemic stroke - Ya-Yu Wang; Shih-Yi Lin; Cheng-Yi Chang; Chih-Cheng Wu; Wen-Ying Chen; Wei-Chi Huang; Su-Lan Liao; Wen-Yi Wang; Chun-Jung Chen (Metabolic Brain Disease, 2023)

A novel BC/g-C3N4 porous hydrogel carrier used in intimately coupled photocatalysis and biodegradation system for efficient removal of tetracycline hydrochloride in water - Huanjun Zhang; Yanan Yu; Yi Li; Li Lin; Chi Zhang; Wenlong Zhang; Longfei Wang; Lihua Niu (Chemosphere, 2023)

The thermal degradation and soil recovery of thermal treatment of field-weathered decabrominated diphenyl ether-contaminated soil - Jennifer Ia Wen Wen Liu; Yu-Jie Lin; Chi-Fong Ko; Jiann-yuan Ding; Yang-hsin Shih (Chemosphere, 2023)

Using HRMS fingerprinting to explore micropollutant contamination in soil and vegetables caused by swine wastewater irrigation - Wen-Ling Chen; Sih-Yi Yu; Shu-Yen Liu; Sheng-Chi Lin; Tsung-Han Lee (Science of The Total Environment, 2023)

Aflatoxin B1 exposure triggers hepatic lipotoxicity via p53 and perilipin 2 interaction-mediated mitochondria-lipid droplet contacts: An in vitro and in vivo assessment - Lin Che; Jing Huang; Jin-Xian Lin; Chi-Yu Xu; Xin-Mou Wu; Ze-Bang Du; Jia-Shen Wu; Zhong-Ning Lin; Yu-Chun Lin (Journal of Hazardous Materials, 2023)

Dynamic change of oligopeptides and free amino acids composition in five types of tea with different fermentation degree processed from the same batch of fresh tea (Camelilia Sinensis. L.) leaves - Feng Zhao; Wenxi Wu; Chi Wang; Xiaojuan Wang; Hui Liu; Jiang Qian; Chunping Cai; Yong Xie; Yu Lin (Food Chemistry, 2023)

Ambient relative humidity-dependent obstructive sleep apnea severity in cold season: A case-control study - Kuan-Jen Bai; Wen-Te Liu; Yuan-Chien Lin; Yansu He; Yueh-Lun Lee; Dean Wu; Ta-Yuan Chang; Li-Te Chang; Chun-Yeh Lai; Cheng-Yu Tsai; Kian Fan Chung; Kin-Fai Ho; et al. (Science of The Total Environment, 2023)

Solar photodegradation of the UV filter benzotriazole in the presence of persulfate - Shih-Chieh Lai; Hank Hui-Hsiang Lin; Jheng-Sian Yang; Ming-Chi Hsieh; Angela Yu-Chen Lin (Journal of Environmental Chemical Engineering, 2023)

Universal correlation for falling film evaporation on a horizontal plain tube - Hao-Yu Lin; Muneeshwaran M; Cheng-Min Yang; Kashif Nawaz; Chi-Chuan Wang (International Journal of Refrigeration, 2023)

On the occurrence of low concentration hyperpycnal river plumes in a small mountainous river-canyon system - Sheng-De Tsai; Yu-Chi Lin; Andhy Romdani; Jia-Lin Chen; Ray T. Hsu; James T. Liu (Continental Shelf Research, 2023)

Source-specific health risk analysis on atmospheric hazardous volatile organic compounds (HVOCs) in Nanjing, East China - Yu-Chi Lin; Zi-Jin Zhang; Meng-Yao Cao; Mei-Yi Fan; Ahsan Mozaffar; Ming-Yuan Yu; Feng Xie; Yan-Lin Zhang (Atmospheric Environment, 2023)

Seasonal variations of low molecular alkyl amines in PM2.5 in a North China Plain industrial city: Importance of secondary formation and combustion emissions - Xiao-Ying Yang; Fang Cao; Mei-Yi Fan; Yu-Chi Lin; Feng Xie; Yan-Lin Zhang (Science of The Total Environment, 2023)

Microbiome reengineering by four environmental factors for the rapid biodegradation of trichloroethylene - Yu-Hsuan Cheng; Shu-Chi Chang; Yan-Lin Lai; Chung-Chi Hu (Journal of Environmental Management, 2023)

Using cluster algorithms with a machine learning technique and PMF models to quantify local-specific origins of PM2.5 and associated metals in Taiwan - Chin-Yu Hsu; Jhy-Charm Soo; Sheng-Lun Lin; Chih-Da Wu; Kai Hsien Chi; Wen-Chang Hsu; Chun-Chieh Tseng; Yu-Cheng Chen (Environmental Pollution, 2023)

Realizing the bifunctional electrocatalysis via local charge rearrangement of α-CrOOH-modulated Co@CoMoOx for overall water splitting - Suh-Ciuan Lim; Chao-Lung Chiang; Chun-Kuo Peng; Wen-Bin Wu; Yu-Chang Lin; Yu-Ru Lin; Chi-Liang Chen; Yan-Gu Lin (Chemical Engineering Journal, 2023)

Intelligent films of marine polysaccharides and purple cauliflower extract for food packaging and spoilage monitoring - Han-Lun Huang; I-Lin Tsai; Chi Lin; Yu-Hao Hang; Yi-Cheng Ho; Min-Lang Tsai; Fwu-Long Mi (Carbohydrate Polymers, 2023)

Quantification of fossil and non-fossil sources to the reduction of carbonaceous aerosols in the Yangtze River Delta, China: Insights from radiocarbon analysis during 2014–2019 - Mingyuan Yu; Yan-Lin Zhang; Tian Xie; Wenhuai Song; Yu-Chi Lin; Yuxian Zhang; Fang Cao; Chi Yang; Sӧnke Szidat (Atmospheric Environment, 2023)

Mesenchymal Stem Cell Secreted-Extracellular Vesicles are Involved in Chondrocyte Production and Reduce Adipogenesis during Stem Cell Differentiation - Yu-Chen Tsai; Tai-Shan Cheng; Hsiu-Jung Liao; Ming-Hsi Chuang; Hui-Ting Chen; Chun-Hung Chen; Kai-Ling Zhang; Chih-Hung Chang; Po-Cheng Lin; Chi-Ying F. Huang (Tissue Engineering and Regenerative Medicine, 2022)
Background: Extracellular vesicles (EVs) are derived from internal cellular compartments, and have potential as a diagnostic and therapeutic tool in degenerative disease associated with aging. Mesenchymal stem cells (MSCs) have become a promising tool for functional EVs production. This study investigated the efficacy of EVs and its effect on differentiation capacity. Methods: The characteristics of MSCs were evaluated by flow cytometry and stem cell differentiation analysis, and a production mode of functional EVs was scaled from MSCs. The concentration and size of EVs were quantitated by Nanoparticle Tracking Analysis (NTA). Western blot analysis was used to assess the protein expression of exosome-specific markers. The effects of MSC-derived EVs were assessed by chondrogenic and adipogenic differentiation analyses and histological observation. Results: The range of the particle size of adipose-derived stem cells (ADSCs)- and Wharton’s jelly -MSCs-derived EVs were from 130 to 150 nm as measured by NTA, which showed positive expression of exosomal markers. The chondrogenic induction ability was weakened in the absence of EVs in vitro . Interestingly, after EV administration, type II collagen, a major component in the cartilage extracellular matrix, was upregulated compared to the EV-free condition. Moreover, EVs decreased the lipid accumulation rate during adipogenic induction. Conclusion: The results indicated that the production model could facilitate production of effective EVs and further demonstrated the role of MSC-derived EVs in cell differentiation. MSC-derived EVs could be successfully used in cell-free therapy to guide chondrogenic differentiation of ADSC for future clinical applications in cartilage regeneration.

7,8-Dihydroxyflavone attenuates the virulence of Staphylococcus aureus by inhibiting alpha-hemolysin - Nan Bian; Xiangqian Chen; Xinran Ren; Zishu Yu; Mengli Jin; Xiaoyu Chen; Chang Liu; Yanhe Luan; Lin Wei; Ying Chen; Wu Song; Yicheng Zhao; et al. (World Journal of Microbiology and Biotechnology, 2022)

Evaluation of the Potential of the Hard Clam (Meretrix meretrix) Shell Which Can Be Used as the Bioindicator for Heavy Metal Accumulation - Yen-Ting Lin; Fang-Chi Chang; Ming-Tsung Chung; Ze-Kai Li; Chang-Chuan Chan; Ying-Sheng Huang; Kuo-Fang Huang; Yu-San Han (Fishes, 2022)
Clams, Meretrix meretrix, were one of the favorite aquatic products in Taiwan and the world. It was reported that the water pollutants such as heavy metals and chemicals might accumulate in the clam body and shell through filter-feeding behavior. Thus, the bivalves could be used as bioindicators in the aquatic environment. The present study analyzed 20 trace elements, Mg, Sr, Li, Cd, Ba, Mn, Al, U, Ti, Pb, Nd, B, S, Zn, Fe, P, Na, K, Cu, and Ni, in the shells of the clams collected from the wild coastal area and cultured ponds to evaluate which elements have the potential to be biomarkers. The concentrations of 20 elements were detected by Solution-Based Inductively Coupled Plasma Mass Spectrometry (SB-ICPMS). Among them, Cd, Al, U, Ti, Nd, S, and K were below the detection limit. The remaining elements were analyzed for accumulation. The levels of Zn, Fe, and Ni possess high variation in an identical environment; so, a PCA was conducted without these three elements to reduce noise. The PCA result proved that the clam could absorb specific trace elements from the habitat. After a period of time, the contents of the absorption in the shells of the clams living in an identical environment became more similar. The analyzed element, Pb, was not found with a special difference in this study. The levels of Na, Sr, Mg, B, Mn, P, Ba, Li, and Cu reflected different sampling sites, which suggested that these elements in the species M. meretrix had the potential to be used as biomarkers for assessing heavy metal accumulation in the environment.

Biomechanical Analysis of Mandibular Implant-Assisted Removable Partial Denture with Distal Extension - Yung-Chung Chen; Chi-Lun Lin; Chen-Han Yu; Hung-Chih Chang; Yang-Ming Lin; Jia-Wei Lin (Journal of Medical and Biological Engineering, 2022)

Isolation and identification of two new sargentodoxosides from Sargentodoxa cuneata and their agonistic effects against FXR - Wen Zhang; Cheng-Peng Sun; Yu-Lin Peng; Wen-Yu Zhao; Zheng-Yue Wang; Jing Ning; Xia Lv; Zhen-Long Yu; Shuang Zhou; Wei Peng; Bang-Jiang Fang; Xiao-Chi Ma (Natural Product Research, 2022)

Fine particulate matter measured by satellites predicts the risk of age-related macular degeneration in a longitudinal cohort study - Chung-Ling Liang; Chi-Min Wang; Chau-Ren Jung; Ya-Chu Chang; Chun-Ju Lin; Yu-Ting Lin; Bing-Fang Hwang (Environmental Science and Pollution Research, 2022)

Anti-inflammatory constituents from Phyllostachys makinoi Hayata - Chia-Ching Liaw; Yu-Chi Lin; Shao-Yu Wu; Jenny Chun-Ling Kuo; Zhi-Hu Lin; Kai-Wei Lin; Huang Hui-Chi; Li-Ming Yang Kuo; Yao-Haur Kuo (Natural Product Research, 2022)

Application of Soil and Water Assessment Tool (SWAT) to evaluate the fates of nitrogenous fertilizer in subtropical mountainous watershed tea farms - Guan-Zhou Lin; Shao-Yiu Hsu; Chia-Chun Ho; Chi-Feng Chen; Jr-Chuan Huang; Tsung-Yu Lee (Environmental Monitoring and Assessment, 2022)

Prevalence, complete genome, and metabolic potentials of a phylogenetically novel cyanobacterial symbiont in the coral‐killing sponge, Terpios hoshinota - Yu‐Hsiang Chen; Hsing‐Ju Chen; Cheng‐Yu Yang; Jia‐Ho Shiu; Daphne Z. Hoh; Pei‐Wen Chiang; Wenhua Savanna Chow; Chaolun Allen Chen; Tin‐Han Shih; Szu‐Hsien Lin; Chi‐Ming Yang; James Davis Reimer; et al. (Environmental Microbiology, 2022)
Summary Terpios hoshinota is an aggressive, space‐competing sponge that kills various stony corals. Outbreaks of this species have led to intense damage to coral reefs in many locations. Here, the first large‐scale 16S rRNA gene survey across three oceans revealed that bacteria related to the taxa Prochloron , Endozoicomonas , SAR116, Ruegeria , and unclassified Proteobacteria were prevalent in T . hoshinota . A Prochloron ‐related bacterium was the most dominant and prevalent cyanobacterium in T . hoshinota . The complete genome of this uncultivated cyanobacterium and pigment analysis demonstrated that it has phycobiliproteins and lacks chlorophyll b , which is inconsistent with the definition of Prochloron . Furthermore, the cyanobacterium was phylogenetically distinct from Prochloron , strongly suggesting that it should be a sister taxon to Prochloron . Therefore, we proposed this symbiotic cyanobacterium as a novel species under the new genus Candidatus Paraprochloron terpiosi. Comparative genomic analyses revealed that ‘Paraprochloron’ and Prochloron exhibit distinct genomic features and DNA replication machinery. We also characterized the metabolic potentials of ‘Paraprochloron terpiosi’ in carbon and nitrogen cycling and propose a model for interactions between it and T. hoshinota . This study builds a foundation for the study of the T . hoshinota microbiome and paves the way for better understanding of ecosystems involving this coral‐killing sponge.

A First Insight Into the Heat-Induced Changes in Proteomic Profiles of the Coral Symbiotic Bacterium Endozoicomonas montiporae - Ya-Fan Chan; Chia-Yu Chen; Chih-Ying Lu; Yung-Chi Tu; Kshitij Tandon; Shinya Shikina; Sen-Lin Tang (Frontiers in Marine Science, 2022)
Endozoicomonas , a core bacterial group in corals, may also be a coral symbiont. Endozoicomonas communities often decrease rapidly in corals under heat stress. However, how the bacteria respond to changes in temperature and coral host during heat stress is unknown. Here, we employed the cultivable, dominant species E. montiporae as a working organism to explore how Endozoicomonas responds to heat stress. We designed two experiments to clarify the extent to which E. montiporae is influenced by temperature and coral host. We detected differentially expressed protein (DEP) profiles in this bacterium at 31 and 33°C compared to 25°C by tandem mass tags-based quantitative proteome analysis. Fifty DEPs, including many heat shock proteins, were detected when the temperature changed. The expression of antioxidant defense proteins and key pyruvate synthase proteins decreased, suggesting that E. montiporae were in a physiology of stress at 33°C. Furthermore, some proteins were differentially expressed because of the heat-stress-treated coral lysate specifically, suggesting that not only heat but also heat-induced host factors can affect the protein expression of the bacterium. This study provides an in-depth analysis of how the molecular mechanisms of Endozoicomonas are affected by heat stress and coral host.

Downregulated Calcium-Binding Protein S100A16 and HSP27 in Placenta-Derived Multipotent Cells Induce Functional Astrocyte Differentiation - Yu-Che Cheng; Chi-Jung Huang; Wei-Chi Ku; Shu-Lin Guo; Lu-Tai Tien; Yih-Jing Lee; Chih-Cheng Chien (Stem Cell Reviews and Reports, 2022)
Little is known about genes that induce stem cells differentiation into astrocytes. We previously described that heat shock protein 27 (HSP27) downregulation is directly related to neural differentiation under chemical induction in placenta-derived multipotent stem cells (PDMCs). Using this neural differentiation cell model, we cross-compared transcriptomic and proteomic data and selected 26 candidate genes with the same expression trends in both omics analyses. Those genes were further compared with a transcriptomic database derived from Alzheimer’s disease (AD). Eighteen out of 26 candidates showed opposite expression trends between our data and the AD database. The mRNA and protein expression levels of those candidates showed downregulation of HSP27, S100 calcium-binding protein A16 (S100A16) and two other genes in our neural differentiation cell model. Silencing these four genes with various combinations showed that co-silencing HSP27 and S100A16 has stronger effects than other combinations for astrocyte differentiation. The induced astrocyte showed typical astrocytic star-shape and developed with ramified, stringy and filamentous processes as well as differentiated endfoot structures. Also, some of them connected with each other and formed continuous network. Immunofluorescence quantification of various neural markers indicated that HSP27 and S100A16 downregulation mainly drive PDMCs differentiation into astrocytes. Immunofluorescence and confocal microscopic images showed the classical star-like shape morphology and co-expression of crucial astrocyte markers in induced astrocytes, while electrophysiology and Ca 2+ influx examination further confirmed their functional characteristics. In conclusion, co-silencing of S100A16 and HSP27 without chemical induction leads to PDMCs differentiation into functional astrocytes. Graphical abstract

Research on hoop capacity of composite foundation of discarded rubber tires - Feng-Chi Wang; Jun Li; Zhen-Huan Lin; Pei-Pei Tian; Han-Yu Zhao (European Journal of Environmental and Civil Engineering, 2022)

Realization of Natural Human Motion on a 3D Biped Robot For Studying the Exoskeleton Effective - Chi-Ying Lee; Shih Chieh Lan; Jung-Ji Lin; Yu-Ting Lin; Po-Shen Chiang; Wei-Li Hsu; Kuo-Kuang Jen; Andy Y. S. Huang; Jia-Yush Yen (Journal of Medical and Biological Engineering, 2021)

The Rapidly Evolving Fudu Estuary Sandbar Lagoon Landform on the East Coast of the Bohai Sea: Recent Changes and Mechanism - Lianjie Zhang; Jishun Yan; Bo Zhao; Xia Lin; Peng Wang; Chi Zhang; Yonghai Yu; Pan Zhang (Journal of Marine Science and Engineering, 2021)
The Fudu Estuary Sandbar Lagoon is one of the most representative sandbar-lagoon landforms in China, and has undergone drastic evolution in recent years, accompanied by increased coastal engineering activities. The evolution process and its control factors are studied through remote sensing interpretation and coastal sediment transport calculations. During 2010–2021, the sandbar quickly extended at an average speed of 49.5 m/a, but the annual growth has shown a decreasing trend in both area and width, and the shoreline has retreated by 25–45 m. The recent changes are the result of the combined action of natural conditions and human activities. Coastal sediment transport from west to east under the action of W-oriented waves is the natural cause of extension. An estuary dam and artificial island block the sediment transport path, and the material for the new growth of the sandbar comes from the erosion of its west side, which has directly caused the retreat and narrowing of the sandbar. The reduction in sediments from the river further aggravates the shrinkage. It is predicted that the sandbar will continue its eastward extension to connect with the coast in about 2–3 years. The erosion status is unlikely to change before the sediment supply is restored. Measures such as dismantling the estuary dam are recommended.

A New Instrumental Array in Sichuan, China, to Monitor Vibrations and Perturbations of the Lithosphere, Atmosphere, and Ionosphere - Chieh-Hung Chen; Yang-Yi Sun; Kai Lin; Chen Zhou; Rui Xu; Haiyin Qing; Yongxin Gao; Tao Chen; Fei Wang; Huaizhong Yu; Peng Han; Chi-Chia Tang; et al. (Surveys in Geophysics, 2021)

Three new species of Cylindrobasidium (Physalacriaceae, Agaricales) from East Asia - Yi-Chung Lin; Chia-Ling Wei; Chi-Yu Chen; Che-Chih Chen; Sheng-Hua Wu (Mycological Progress, 2021)

Anti-Inflammatory and anti-proliferative oleanane-type triterpene glycosides from the vine of Momordica cochinchinensis - Hung-Tse Huang; Yu-Chi Lin; Li-Jie Zhang; Chia-Ching Liaw; Hsin-Yen Chen; Ming-Tung Hsueh; Yao-Haur Kuo (Natural Product Research, 2021)

Wogonin Accelerates Hematoma Clearance and Improves Neurological Outcome via the PPAR-γ Pathway After Intracerebral Hemorrhage - Jianfeng Zhuang; Yucong Peng; Chi Gu; Huihui Chen; Zheng Lin; Hang Zhou; Xiao Wu; Jianru Li; Xiaobo Yu; Yang Cao; Hanhai Zeng; Xiongjie Fu; et al. (Translational Stroke Research, 2021)

Efficacy of Entomopathogenic fungus Aspergillus nomius against Dolichoderus thoracicus - Wei-Jiun Lin; Ming-Chung Chiu; Chung-Chi Lin; Yuan-Kai Chung; Jui-Yu Chou (BioControl, 2021)

Environmental microorganism classification using optimized deep learning model - Chih-Ming Liang; Chun-Chi Lai; Szu-Hong Wang; Yu-Hao Lin (Environmental Science and Pollution Research, 2021)

A dye combination for the staining of pollen coat and pollen wall - Xin-Lei Jia; Jing-Shi Xue; Fang Zhang; Chi Yao; Shi-Yi Shen; Chang-Xu Sui; Yu-Jia Peng; Qin-Lin Xu; Yi-Feng Feng; Wen-Jing Hu; Ping Xu; Zhong-Nan Yang (Plant Reproduction, 2021)

Computed Tomography Super-Resolution Using a Generative Adversarial Network in Bronchoscopy: A Clinical Feasibility Study - Heng-sheng Chao; Tsu-Hui Shiao; Chung-Wei Chou; Fang-Chi Lin; Yu-Te Wu; Der-Ming Liou (Journal of Medical and Biological Engineering, 2021)

MiR-124 and Small Molecules Synergistically Regulate the Generation of Neuronal Cells from Rat Cortical Reactive Astrocytes - Yangyang Zheng; Zhehao Huang; Jinying Xu; Kun Hou; Yifei Yu; Shuang Lv; Lin Chen; Yulin Li; Chengshi Quan; Guangfan Chi (Molecular Neurobiology, 2021)

Influence of different fluidization and gasification parameters on syngas composition and heavy metal retention in a two-stage fluidized bed gasification process - Jia-Hong Kuo; Chiou-Liang Lin; Chang-Yu Ho; Jia-Chi Hung (Environmental Science and Pollution Research, 2021)

New secondary metabolite with cytotoxicity from spawning soft coral Asterospicularia laurae in Taiwan - Jui-Hsin Su; Chih-I Liu; Mei-Chin Lu; Chi-I Chang; Min-Ying Hsieh; Yu-Chi Lin; Chang-Feng Dai; Ya-Han Zhang; Zheng-Yu Lin; Yun-Sheng Lin (Natural Product Research, 2021)

Syndecan-3 contributes to the regulation of the microenvironment at the node of Ranvier following end-to‑side neurorrhaphy: sodium image analysis - Chiung-Hui Liu; Yu-Chen Kuo; Che-Yu Wang; Chao-Chun Hsu; Ying-Jui Ho; Yun-Chi Chiang; Fu-Der Mai; Wei-Jhih Lin; Wen-Chieh Liao (Histochemistry and Cell Biology, 2021)

Direct Calculation Method for the Analysis of Non-linear Behavior of Ground-Support Interaction of a Circular Tunnel Using Convergence Confinement Approach - Yu-Lin Lee; Wen-Kuei Hsu; Chi-Min Lee; Yi-Xian Xin; Bo-Yu Zhou (Geotechnical and Geological Engineering, 2021)

Optimizing the MIC breakpoints of amoxicillin and tetracycline for antibiotic selection in the rescue therapy of H. pylori with bismuth quadruple regimen - Ming-Tsung Hsieh; Wei-Lun Chang; Chung-Tai Wu; Hsiao-Bai Yang; Hsin-Yu Kuo; Meng-Ying Lin; Hsiu-Chi Cheng; Yu-Chin Tsai; Bor-Shyang Sheu (European Journal of Clinical Pharmacology, 2020)

A new macrocyclic diterpenoid from Anisomeles indica - Chen-Liang Chao; Hui-Chi Huang; Hsiou-Yu Ding; Jenn-Haung Lai; Hang-Ching Lin; Wen-Liang Chang (Natural Product Research, 2020)

Feasibility of using bed filters packed with rice-straw-based activated carbon and selected biomass waste for the control of frying fume exhaust - Yen-Chi Chen; Xuan-En Yang; Kun-Yi Lin; Wei-Wen Huang; Chi-Chi Lin; Kuo-Pin Yu (Environmental Science and Pollution Research, 2020)

Small RNA profiling reveal regulation of microRNAs in field peanut pod rot pathogen infection - Mian Wang; Chao-xin Zhang; Li-juan Pan; Tong Wang; Na Chen; Ming-na Chen; Zhen Yang; Xin-gang Guo; Shan-lin Yu; Xiao-yuan Chi (Biologia, 2020)

Evaluating the severity of building fires with the analytical hierarchy process, big data analysis, and remote sensing - Ching-An Lee; Yu-Chi Sung; Yuan-Shang Lin; Gary Li-Kai Hsiao (Natural Hazards, 2020)

TNFSF13 upregulation confers chemotherapeutic resistance via triggering autophagy initiation in triple-negative breast cancer - Hui-Yu Lin; Chia-Hao Kuei; Hsun-Hua Lee; Che-Hsuan Lin; Yen-Lin Chen; Chi-Long Chen; Yuan-Feng Lin (Journal of Molecular Medicine, 2020)

On the mechanism of soft clay being improved entirely in the ECT treatment - Chang-Yu Ou; Chien-Yu Lin; Shao-Chi Chien (Bulletin of Engineering Geology and the Environment, 2020)

Household airborne endotoxin associated with asthma and allergy in elementary school-age children: a case–control study in Kaohsiung, Taiwan - Yu-Chuan Yen; Chun-Yuh Yang; Tsu-Nai Wang; Pei-Chun Yen; Chi-Kung Ho; Kristina D. Mena; Tzu-Chi Lee; Kang-Shin Chen; Yuan-Chung Lin; Pei-Shih Chen (Environmental Science and Pollution Research, 2020)
To evaluate the association between the presence of asthma and allergy, and airborne endotoxin in homes of school-age children in Kaohsiung City, Taiwan, with a case–control study design by matching the age and class exposure. Data collection of home visits included an interviewer-administered questionnaire and air sampling of participants’ homes for endotoxin, bacteria, and fungi, as well as temperature and relative humidity measurements. Endotoxin was detected in all air samples with a median value of 0.67 EU m −3 . In the adjusted logistic regression model, household airborne endotoxin was associated with higher prevalence of asthma and allergy; OR = 4.88 (95% CI 1.16–20.55) for Q3 (between 0.67 and 1.97 EU m −3 ) vs. Q1 (< 0.31 EU m −3 ), with statistical significance. Airborne fungi were associated with higher prevalence of asthma and allergy; OR = 4.47 (95% CI 1.13–17.69) for Q3 (between 314 and 699 CFU m −3 ) vs. Q1 (< 159 CFU m −3 ) in adjusted logistic regression models. Airborne endotoxin and fungi were significantly associated with children’s asthma and allergy.

Combined effect of polymorphisms of MTHFR and MTR and arsenic methylation capacity on developmental delay in preschool children in Taiwan - Yu-Mei Hsueh; Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Horng-Sheng Shiue; Ssu-Ning Chien; Chih-Ying Lee; Ming-I. Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2020)

The evaluation of BTEX and carbonyls emissions from recycled building materials - Yu-Hsiang Cheng; Chi-Chi Lin; Yun-Tai Lee; Yu-Chun Lin (Environmental Monitoring and Assessment, 2020)

Prior Antiplatelet Therapy, Excluding Phosphodiesterase Inhibitor Is Associated with Poor Outcome in Patients with Spontaneous Intracerebral Haemorrhage - Zhuo-Hao Liu; Chi-Hung Liu; Po-Hsun Tu; Ping K. Yip; Ching-Chang Chen; Yu-Chi Wang; Nan-Yu Chen; Yu-Sheng Lin (Translational Stroke Research, 2020)

Assessing dietary exposure risk to neonicotinoid residues among preschool children in regions of Taiwan - Min-Pei Ling; Huai-An Hsiao; Szu-Chieh Chen; Wei-Yu Chen; Wei-Chun Chou; Yi-Jun Lin; Shu-Han You; Ying-Fei Yang; Hsing-Chieh Lin; Chi-Yun Chen; Tien-Hsuan Lu; Chung-Min Liao (Environmental Science and Pollution Research, 2020)

Spatiotemporal assessment of mortality attributable to ambient PM2.5 exposure in Taiwan during 2008–2015 - Su-Lun Hwang; Yu-Ching Lin; Kuang-Yu Hsiao; Chieh-Mo Lin; Miao-Ching Chi (Air Quality, Atmosphere & Health, 2020)

Gallic Acid Attenuated LPS-Induced Neuroinflammation: Protein Aggregation and Necroptosis - Yu-Ling Liu; Chia-Chi Hsu; Hui-Ju Huang; Chih-Jung Chang; Shu-Hui Sun; Anya Maan-Yuh Lin (Molecular Neurobiology, 2020)

Sarocladium species associated with rice in Taiwan - Jie-Hao Ou; Guo-Cih Lin; Chi-Yu Chen (Mycological Progress, 2020)

Correction to: Soluble Epoxide Hydrolase Inhibition Attenuates Excitotoxicity Involving 14,15-Epoxyeicosatrienoic Acid–Mediated Astrocytic Survival and Plasticity to Preserve Glutamate Homeostasis - Yi-Min Kuo; Pei-Chien Hsu; Chia-Chi Hung; Ya-Yu Hu; Yu-Jie Huang; Yu-Ling Gan; Chun-Hua Lin; Feng-Shiun Shie; Wen-Kuei Chang; Lung-Sen Kao; Mei-Yung Tsou; Yi-Hsuan Lee (Molecular Neurobiology, 2019)

Soluble Epoxide Hydrolase Inhibition Attenuates Excitotoxicity Involving 14,15-Epoxyeicosatrienoic Acid–Mediated Astrocytic Survival and Plasticity to Preserve Glutamate Homeostasis - Yi-Min Kuo; Pei-Chien Hsu; Chia-Chi Hung; Ya-Yu Hu; Yu-Jie Huang; Yu-Ling Gan; Chun-Hua Lin; Feng-Shiun Shie; Wen-Kuei Chang; Lung-Sen Kao; Mei-Yung Tsou; Yi-Hsuan Lee (Molecular Neurobiology, 2019)

Mutational signatures and mutagenic impacts associated with betel quid chewing in oral squamous cell carcinoma - Shih-Chi Su; Lun-Ching Chang; Chiao-Wen Lin; Mu-Kuan Chen; Chun-Ping Yu; Wen-Hung Chung; Shun-Fa Yang (Human Genetics, 2019)

Pathological and therapeutic aspects of matrix metalloproteinases: implications in childhood leukemia - Yi-Hsuan Hsiao; Shih-Chi Su; Chiao-Wen Lin; Yu-Hua Chao; Wei-En Yang; Shun-Fa Yang (Cancer and Metastasis Reviews, 2019)

Association of plasma folate, vitamin B12 levels, and arsenic methylation capacity with developmental delay in preschool children in Taiwan - Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Pui-Lam Ao; Horng-Sheng Shiue; Shiau-Rung Huang; Chien-Tien Su; Ming-I Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2019)

PARK14 (D331Y) PLA2G6 Causes Early-Onset Degeneration of Substantia Nigra Dopaminergic Neurons by Inducing Mitochondrial Dysfunction, ER Stress, Mitophagy Impairment and Transcriptional Dysregulation in a Knockin Mouse Model - Ching-Chi Chiu; Chin-Song Lu; Yi-Hsin Weng; Ying-Ling Chen; Ying-Zu Huang; Rou-Shayn Chen; Yi-Chuan Cheng; Yin-Cheng Huang; Yu-Chuan Liu; Szu-Chia Lai; Kun-Jun Lin; Yan-Wei Lin; et al. (Molecular Neurobiology, 2019)

Exercise Rehabilitation Attenuates Cognitive Deficits in Rats with Traumatic Brain Injury by Stimulating the Cerebral HSP20/BDNF/TrkB Signalling Axis - Willy Chou; Yu-Fan Liu; Cheng-Hsien Lin; Mao-Tsun Lin; Chi-Chun Chen; Wen-Pin Liu; Ching-Ping Chang; Chung-Ching Chio (Molecular Neurobiology, 2018)

Response to “Letter to the editor re: Cheng YH, Chou WC, Yang YF, et al. Environ Sci Pollut Res (2018). https://doi.org/10.107/s11356-017-0875-4” - Yi-Hsien Cheng; Wei-Chun Chou; Ying-Fei Yang; Chi-Wei Huang; Chun Ming How; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Shu-Han You; Chung-Min Liao (Environmental Science and Pollution Research, 2018)

Sodium Metabisulfite: Effects on Ionic Currents and Excitotoxicity - Ming-Chi Lai; Te-Yu Hung; Kao-Min Lin; Pi-Shan Sung; Shyh-Jong Wu; Chih-Sheng Yang; Yi-Jen Wu; Jing-Jane Tsai; Sheng-Nan Wu; Chin-Wei Huang (Neurotoxicity Research, 2018)

Peri-Therapeutic Quantitative Flow Analysis of Endovascular Revascularization for Ischemic Stroke Patients on Digital Subtraction Angiography - Shih-Neng Yang; Yu-Yi Lin; Tsung-Jung Ho; Shi-Yann Cheng; Yu-Rou Chiou; Chun-Han Liao; Geoffrey G. Zhang; Tzung-Chi Huang (Journal of Medical and Biological Engineering, 2018)

Rice ecosystem services in South-east Asia - Josef Settele; Kong Luen Heong; Ingolf Kühn; Stefan Klotz; Joachim H. Spangenberg; Gertrudo Arida; Alexis Beaurepaire; Silke Beck; Erwin Bergmeier; Benjamin Burkhard; Roland Brandl; Jesus Victor Bustamante; et al. (Paddy and Water Environment, 2018)

Seasonal variation and source apportionment of PM2.5-bound trace elements at a coastal area in southwestern Taiwan - Su-Lun Hwang; Miao-Ching Chi; Su-Er Guo; Yu-Ching Lin; Chiang-Ting Chou; Chieh-Mo Lin (Environmental Science and Pollution Research, 2018)

MiR-26a functions as a tumor suppressor in ambient particulate matter-bound metal-triggered lung cancer cell metastasis by targeting LIN28B–IL6–STAT3 axis - Yan-Yang Lu; Yi Lin; Dong-Xiao Ding; Shu Su; Qiao-Qiao Chi; You-Chi Zhang; Jian Sun; Xu Zhang; Hui-Min Zhu; Qian-Sheng Huang; Yu-Lang Chi; Guo-Zhu Ye; et al. (Archives of Toxicology, 2018)

Dose Verification for Tumor Motion with Different Treatment Planning Systems: A Dynamic Thorax Phantom Study - Shih-Neng Yang; Chun-Wei Lin; Mu-Bai Chang; Geoffrey G. Zhang; Kuei-Ting Chou; Yu-Rou Chiou; Shung-Shung Sun; Louis Lui; Tsung-Jung Ho; Tzung-Chi Huang (Journal of Medical and Biological Engineering, 2018)

PBPK/PD assessment for Parkinson’s disease risk posed by airborne pesticide paraquat exposure - Yi-Hsien Cheng; Wei-Chun Chou; Ying-Fei Yang; Chi-Wei Huang; Chun Ming How; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Shu-Han You; Chung-Min Liao (Environmental Science and Pollution Research, 2018)

Prevalence, mechanisms and genetic relatedness of the human pathogenic fungus Aspergillus fumigatus exhibiting resistance to medical azoles in the environment of Taiwan - Hsuan‐Chen Wang; Jui‐Chang Huang; Yong‐Hong Lin; Yu‐Hsin Chen; Ming‐I Hsieh; Pui‐Ching Choi; Hsiu‐Jung Lo; Wei‐Lun Liu; Ching‐Shan Hsu; Hsin‐I Shih; Chi‐Jung Wu; Yee‐Chun Chen (Environmental Microbiology, 2018)
Summary Emerging azole resistance in Aspergillus fumigatus poses a serious threat to human health. This nationwide surveillance study investigated the prevalence and molecular characteristics of azole‐resistant A. fumigatus environmental isolates in Taiwan, an island country with increasing use of azole fungicides. Of the 2760 air and soil samples screened from 2014 to 2016, 451 A. fumigatus isolates were recovered from 266 samples and 34 isolates from 29 samples displayed resistance to medical azoles (itraconazole, voriconazole or posaconazole). The resistance prevalence was 10.9% and 7.5% in A. fumigatus ‐positive samples and isolates respectively. Most (29, 85.3%) azole‐resistant isolates harboured TR 34 /L98H mutations, which were widely distributed, clustered genetically with clinical isolates, and had growth rates that were similar to those of the wild‐type isolates. Microsatellite genotyping revealed both the global spread of the TR 34 /L98H isolates and the occurrence of TR 34 /L98H/S297T/F495I isolates belonging to local microsatellite genotypes. AfuMDR3 and atrF , two efflux transporter genes, were constitutively upregulated in two individual resistant isolates without cyp51A mutations, highlighting their potential roles in azole resistance. These results emphasize the need for periodic environmental surveillance at the molecular level in regions in which azole fungicides are applied, and agricultural fungicide management strategies that generate less selective pressure should be investigated.

Establishing a Forecast Mathematical Model of Sugarcane Yield and Brix Reduction Based on the Extent of Pokkah Boeng Disease - Ze-ping Wang; Lu Liu; Yu-chi Deng; Yi-jie Li; Ge-min Zhang; Shan-hai Lin; Tie-guang He (Sugar Tech, 2017)

IL-28 and IL-29 as protective markers in subject with dengue fever - Chih-Hsing Hung; Chung-Hao Huang; Lin Wang; Chun-Chi Huang; Meng-Chieh Wu; Yi-Ying Chin; Chun-Yu Lin; Ko Chang; Deng-Chyang Wu; Yen-Hsu Chen (Medical Microbiology and Immunology, 2017)

Cytoplasmic aryl hydrocarbon receptor regulates glycogen synthase kinase 3 beta, accelerates vimentin degradation, and suppresses epithelial–mesenchymal transition in non-small cell lung cancer cells - Ching-Hao Li; Chen-Wei Liu; Chi-Hao Tsai; Yi-Jen Peng; Yu-Hsuan Yang; Po-Lin Liao; Chen-Chen Lee; Yu-Wen Cheng; Jaw-Jou Kang (Archives of Toxicology, 2017)

Pharmacological Inhibition of PERK Attenuates Early Brain Injury After Subarachnoid Hemorrhage in Rats Through the Activation of Akt - Feng Yan; Shenglong Cao; Jianru Li; Brandon Dixon; Xiaobo Yu; Jingyin Chen; Chi Gu; Wang Lin; Gao Chen (Molecular Neurobiology, 2017)

Gap junction protein connexin43 deregulation contributes to bladder carcinogenesis via targeting MAPK pathway - Xiao-lin Ai; Qiang Chi; Yu Qiu; Hong-yang Li; Dong-jie Li; Jia-xu Wang; Zhi-yong Wang (Molecular and Cellular Biochemistry, 2017)

Plasma Amyloid-Beta Levels in Patients with Different Types of Cancer - Wang-Sheng Jin; Xian-Le Bu; Yu-Hui Liu; Lin-Lin Shen; Zhen-Qian Zhuang; Shu-Sheng Jiao; Chi Zhu; Qing-Hua Wang; Hua-Dong Zhou; Tao Zhang; Yan-Jiang Wang (Neurotoxicity Research, 2017)

An integrated earthquake early warning system and its performance at schools in Taiwan - Bing-Ru Wu; Nai-Chi Hsiao; Pei-Yang Lin; Ting-Yu Hsu; Chiou-Yun Chen; Shieh-Kung Huang; Hung-Wei Chiang (Journal of Seismology, 2017)

Goatpoxvirus ATPase activity is increased by dsDNA and decreased by zinc ion - Ming-Liang Lee; Wei-Li Hsu; Chi-Young Wang; Hui-Yu Chen; Fong-Yuan Lin; Ming-Huang Chang; Hong-You Chang; Min-Liang Wong; Kun-Wei Chan (Virus Genes, 2016)

Methylation and Esterification of Magnolol for Ameliorating Cutaneous Targeting and Therapeutic Index by Topical Application - Chwan-Fwu Lin; Chi-Feng Hung; Ibrahim A. Aljuffali; Yu-Ling Huang; Wei-Chun Liao; Jia-You Fang (Pharmaceutical Research, 2016)

Influence of Soluplus on Solid-State Properties and Physical Stability of Indomethacin-Saccharin Co-crystal Formation Prepared by Air-Drying Process - Shan-Yang Lin; Hong-Liang Lin; Ying-Ting Chi; Ru-Ying Hung; Yu-Ting Huang; Wei-Hsien Hsieh; Chi-Yu Kao (Journal of Pharmaceutical Innovation, 2016)

Estrogenic effects in the influents and effluents of the drinking water treatment plants - Yan-You Gou; Susana Lin; Danielle E. Que; Lemmuel L. Tayo; Ding-Yan Lin; Kuan-Chung Chen; Fu-An Chen; Pen-Chi Chiang; Gen-Shuh Wang; Yi-Chyuan Hsu; Kuo Pin Chuang; Chun-Yu Chuang; et al. (Environmental Science and Pollution Research, 2016)

Spatial and Age-Dependent Hair Cell Generation in the Postnatal Mammalian Utricle - Zhen Gao; Michael C. Kelly; Dehong Yu; Hao Wu; Xi Lin; Fang-lu Chi; Ping Chen (Molecular Neurobiology, 2016)

Sex Dimorphism Profile of Alzheimer’s Disease-Type Pathologies in an APP/PS1 Mouse Model - Shu-Sheng Jiao; Xian-Le Bu; Yu-Hui Liu; Chi Zhu; Qing-Hua Wang; Lin-Lin Shen; Cheng-Hui Liu; Ye-Ran Wang; Xiu-Qing Yao; Yan-Jiang Wang (Neurotoxicity Research, 2016)

Effect of resin content and substrate on the emission of BTEX and carbonyls from low-VOC water-based wall paint - Ping Zhao; Yu-Hsiang Cheng; Chi-Chi Lin; Yu-Lin Cheng (Environmental Science and Pollution Research, 2016)

Serum Amyloid-Beta Levels are Increased in Patients with Chronic Obstructive Pulmonary Disease - Xian-Le Bu; Guo-Qiang Cao; Lin-Lin Shen; Yang Xiang; Shu-Sheng Jiao; Yu-Hui Liu; Chi Zhu; Fan Zeng; Qing-Hua Wang; Ye-Ran Wang; Yong He; Hua-Dong Zhou; et al. (Neurotoxicity Research, 2015)

CO Induces Nrf2-Dependent Heme Oxygenase-1 Transcription by Cooperating with Sp1 and c-Jun in Rat Brain Astrocytes - Pei-Ling Chi; Chih-Chung Lin; Yu-Wen Chen; Li-Der Hsiao; Chuen-Mao Yang (Molecular Neurobiology, 2015)

Metabolites of Scutellariae Radix Inhibit Injury of Endothelial Cells in Hypoxia Device - Chia-Lun Chao; Shiuan-Pey Lin; Yu-Chi Hou; Pei-Dawn Lee Chao; Nen-Chung Chang; Yu-Ching Huang; Feng-Ming Ho (Journal of Medical and Biological Engineering, 2015)

Surface Properties and In Vitro Bioactivity of Fluorapatite/TiO2 Coatings Deposited on Ti Substrates by Nd:YAG Laser Cladding - Chi-Sheng Chien; Yu-Sheng Ko; Tsung-Yuan Kuo; Tze-Yuan Liao; Huan-Chang Lin; Tzer-Min Lee; Ting-Fu Hong (Journal of Medical and Biological Engineering, 2015)

Pilot study of mold in homes of asthmatic children in Taipei, Taiwan, using the Environmental Relative Moldiness Index - Chi-Hsien Chen; H. Jasmine Chao; Wei-Chiang Shen; Bing-Yu Chen; King-Teh Lin; Yue Leon Guo; Stephen Vesper (Aerobiologia, 2015)

Geotechnical hazards assessment on wind-eroded desert embankment in Inner Mongolia Autonomous Region, North China - Chi Li; Hao Huang; Lin Li; Yu Gao; Yunfeng Ma; Farshad Amini (Natural Hazards, 2015)

Increase of Zinc Finger Protein 179 in Response to CCAAT/Enhancer Binding Protein Delta Conferring an Antiapoptotic Effect in Astrocytes of Alzheimer’s Disease - Shao-Ming Wang; Yi-Chao Lee; Chiung-Yuan Ko; Ming-Derg Lai; Ding-Yen Lin; Ping-Chieh Pao; Jhih-Ying Chi; Yu-Wei Hsiao; Tsung-Lin Liu; Ju-Ming Wang (Molecular Neurobiology, 2015)

Two Frequent Mutations Associated with the Classic Form of Propionic Acidemia in Taiwan - Yen-Hui Chiu; Yu-Ning Liu; Wei-Ling Liao; Ying-Chen Chang; Shuan-Pei Lin; Chia-Chi Hsu; Pao-Chin Chiu; Dau-Ming Niu; Chung-Hsing Wang; Yu-Yuan Ke; Yin-Hsiu Chien; Kwang-Jen Hsiao; et al. (Biochemical Genetics, 2014)

Isolation and characterization of microsatellite loci in the Chinese water snake Enhydris chinensis (Colubridae) - Yu Du; Xiao-Xiao Zheng; Yun-Tao Yao; Chi-Xian Lin (Conservation Genetics Resources, 2014)

Maintenance of human adipose derived stem cell (hASC) differentiation capabilities using a 3D culture - Ching-Yu Lin; Chi-Hui Huang; Yuan-Kun Wu; Nai-Chen Cheng; Jiashing Yu (Biotechnology Letters, 2014)

Yeast Oropharyngeal Colonization in Human Immunodeficiency Virus-Infected Patients in Central Taiwan - Mao-Wang Ho; Yun-Liang Yang; Chih-Chao Lin; Chih-Yu Chi; Hui-Ting Chen; Po-Chang Lin; Li-Yun Hsieh; Chia-Hui Chou; Wen-Li Chu; Chiou-Pyng Wu; Tsai-Ling Lauderdale; Hsiu-Jung Lo (Mycopathologia, 2014)

Aryl hydrocarbon receptor (AhR) agonists increase airway epithelial matrix metalloproteinase activity - Ming-Ju Tsai; Ya-Lin Hsu; Tsu-Nai Wang; Ling-Yu Wu; Chi-Tun Lien; Chih-Hsing Hung; Po-Lin Kuo; Ming-Shyan Huang (Journal of Molecular Medicine, 2014)

Pulmonary Toxicity in Mice Following Exposure to Cerium Chloride - Jie Hong; Xiaohong Yu; Xiaoyu Pan; Xiaoyang Zhao; Lei Sheng; Xuezi Sang; Anan Lin; Chi Zhang; Yue Zhao; Suxin Gui; Qingqing Sun; Ling Wang; et al. (Biological Trace Element Research, 2014)

Development of microsatellite markers in the gray ratsnake Ptyas korros (Colubridae) - Xiao-Xiao Zheng; Yu Du; Long-Hui Lin; Chi-Xian Lin (Conservation Genetics Resources, 2014)

Development of microsatellite markers in the beauty rat snake Elaphe taeniura (Colubridae) - Xiao-Xiao Zheng; Yu Du; Long-Hui Lin; Chi-Xian Lin (Conservation Genetics Resources, 2014)

Erratum to: Mycena kentingensis, a new species of luminous mushroom in Taiwan, with reference to its culture method - Yu-Shen Shih; Chi-Yu Chen; Wen-Wen Lin; Hsiao-Wei Kao (Mycological Progress, 2014)

Mycena kentingensis, a new species of luminous mushroom in Taiwan, with reference to its culture method - Yu-Shen Shih; Chi-Yu Chen; Wen-Wen Lin; Hsiao-Wei Kao (Mycological Progress, 2014)

Temporal characteristics of black carbon concentrations and its potential emission sources in a southern Taiwan industrial urban area - Yu-Hsiang Cheng; Chi-Chi Lin; Jyh-Jian Liu; Cheng-Ju Hsieh (Environmental Science and Pollution Research, 2014)

A peroxiredoxin cDNA from Taiwanofungus camphorata: role of Cys31 in dimerization - Chih-Yu Huang; Yu-Ting Chen; Lisa Wen; Dey-Chyi Sheu; Chi-Tsai Lin (Molecular Biology Reports, 2014)

Nutrient limitation in Auxenochlorella protothecoides induces qualitative changes of fatty acid and expression of caleosin as a membrane protein associated with oil bodies - Buntora Pasaribu; I-Ping Lin; Chii-Shiarng Chen; Chi-Yu Lu; Pei-Luen Jiang (Biotechnology Letters, 2014)

Enterocin T, a novel class IIa bacteriocin produced by Enterococcus sp. 812 - Yi-sheng Chen; Chi-rong Yu; Si-hua Ji; Min-shiuan Liou; Kun-hon Leong; Shwu-fen Pan; Hui-chung Wu; Yu-hsuan Lin; Bi Yu; Fujitoshi Yanagida (Archives of Microbiology, 2013)

Identification and Characterization of an Extracellular Alkaline Phosphatase in the Marine Diatom Phaeodactylum tricornutum - Hung-Yun Lin; Chi-Yu Shih; Hung-Chun Liu; Jeng Chang; Ying-Lan Chen; Yet-Ran Chen; Han-Tso Lin; Yu-Yung Chang; Chun-Hua Hsu; Han-Jia Lin (Marine Biotechnology, 2013)

Catalog of Erycina pusilla miRNA and categorization of reproductive phase-related miRNAs and their target gene families - Choun-Sea Lin; Jeremy J. W. Chen; Yao-Ting Huang; Chen-Tran Hsu; Hsiang-Chia Lu; Ming-Lun Chou; Li-Chi Chen; Chia-I Ou; Der-Chih Liao; Ysuan-Yu Yeh; Song-Bing Chang; Su-Chen Shen; et al. (Plant Molecular Biology, 2013)

A novel antitubulin agent, DPQZ, induces cell apoptosis in human oral cancer cells through Ras/Raf inhibition and MAP kinases activation - Mann-Jen Hour; Kun-Tsung Lee; Yang-Chang Wu; Chi-Yu Wu; Bang-Jau You; Tai-Lin Chen; Hong-Zin Lee (Archives of Toxicology, 2013)

Hyperinakin, a new anti-inflammatory phloroglucinol derivative from Hypericum nakamurai - Yuan-Bin Cheng; Ahmed Eid Fazary; Yu-Chi Lin; I-Wen Lo; Seow-Chin Ong; Shun-Ying Chen; Ching-Te Chien; Yen-Jung Lin; Wan-Wan Lin; Ya-Ching Shen (Natural Product Research, 2013)

Tail loss compromises immunity in the many-lined skink, Eutropis multifasciata - Chi-Chien Kuo; Chiou-Ju Yao; Te-En Lin; Hsu-Che Liu; Yu-Cheng Hsu; Ming-Kun Hsieh; Wen-San Huang (The Science of Nature, 2013)

The enhancement of biofilm formation in Group B streptococcal isolates at vaginal pH - Yueh-Ren Ho; Chien-Ming Li; Chen-Hsiang Yu; Yuh-Jyh Lin; Ching-Ming Wu; I-Chen Harn; Ming-Jer Tang; Yi-Ting Chen; Fang-Chi Shen; Chien-Yi Lu; Tai-Chun Tsai; Jiunn-Jong Wu (Medical Microbiology and Immunology, 2013)

Accelerated ovarian aging in mice by treatment of busulfan and cyclophosphamide - Yan Jiang; Jing Zhao; Hui-jing Qi; Xiao-lin Li; Shi-rong Zhang; Daniel W. Song; Chi-yang Yu; Jian-gang Gao (Journal of Zhejiang University-SCIENCE B, 2013)

Glycogen synthase kinase-3β inactivation is an intracellular marker and regulator for endotoxemic neutrophilia - Tsan-Tzu Yang; Chia-Ling Chen; Wei-Chieh Lin; Yee-Shin Lin; Po-Chun Tseng; Chia-Yuan Hsieh; Yu-Hong Chen; Wei-Ching Huang; Cheng-Chieh Tsai; Chi-Yun Wang; Chi-Chang Shieh; Chiou-Feng Lin (Journal of Molecular Medicine, 2013)

A molecular diagnosis method using real-time PCR for quantification and detection of Fusarium oxysporum f. sp. cubense race 4 - Ying-Hong Lin; Ching-Chung Su; Chih-Ping Chao; Chi-Yu Chen; Chung-Jan Chang; Jenn-Wen Huang; Pi-Fang Linda Chang (European Journal of Plant Pathology, 2013)

A Mucormycosis Case in a Cirrhotic Patient Successfully Treated with Posaconazole and Review of Published Literature - Shang-Yi Lin; Po-Liang Lu; Kun-Bow Tsai; Chun-Yu Lin; Wei-Ru Lin; Tun-Chieh Chen; Ya-Ting Chang; Chung-Hao Huang; Chi-Yu Chen; Chung-Chih Lai; Yen-Hsu Chen (Mycopathologia, 2012)

Folic acid inhibits endothelial cell proliferation through activating the cSrc/ERK 2/NF-κB/p53 pathway mediated by folic acid receptor - Shyr-Yi Lin; Woan-Ruoh Lee; Yi-Fan Su; Sung-Po Hsu; Hsu-Chen Lin; Pei-Yin Ho; Tien-Chi Hou; Yu-Pei Chou; Chun-Ting Kuo; Wen-Sen Lee (Angiogenesis, 2012)

Albumin prevents reactive oxygen species-induced mitochondrial damage, autophagy, and apoptosis during serum starvation - Shu-Yu Liu; Chia-Ling Chen; Tsan-Tzu Yang; Wei-Ching Huang; Chia-Yuan Hsieh; Wan-Jou Shen; Tsung-Ting Tsai; Chi-Chang Shieh; Chiou-Feng Lin (Apoptosis, 2012)

Interplay of RsbM and RsbK controls the σ B activity of Bacillus cereus - Lei‐Chin Chen; Jung‐Chi Chen; Jwu‐Ching Shu; Chien‐Yen Chen; Ssu‐Ching Chen; Shu‐Hwa Chen; Chun‐Yen Lin; Chi‐Yu Lu; Chien‐Cheng Chen (Environmental Microbiology, 2012)
Summary The alternative transcription factor σ B of Bacillus cereus controls the expression of a number of genes that respond to environmental stress. Four proteins encoded in the sigB gene cluster, including RsbV, RsbW, RsbY (RsbU) and RsbK, are known to be essential in the σ B ‐mediated stress response. In the context of stress, the hybrid sensor kinase RsbK is thought to phosphorylate the response regulator RsbY, a PP2C serine phosphatase, leading to the dephosphorylation of the phosphorylated RsbV. The unphosphorylated RsbV then sequesters the σ B antagonist, RsbW, ultimately liberating σ B . The gene arrangement reveals an open reading frame, bc1007 , flanked immediately downstream by rsbK within the sigB gene cluster. However, little is known about the function of bc1007 . In this study, the deletion of bc1007 resulted in high constitutive σ B expression independent of environmental stimuli, indicating that bc1007 plays a role in σ B regulation. A bacterial two‐hybrid analysis demonstrated that BC1007 interacts directly with RsbK, and autoradiographic studies revealed a specific C 14 ‐methyl transfer from the radiolabelled S‐adenosylmethionine to RsbK when RsbK was incubated with purified BC1007. Our data suggest that BC1007 (RsbM) negatively regulates σ B activity by methylating RsbK. Additionally, mutagenic substitution was employed to modify 12 predicted methylation residues in RsbK. Certain RsbK mutants were able to rescue σ B activation in a rsbK ‐deleted bacterial strain, but RsbK E439A failed to activate σ B , and RsbK E446A only moderately induced σ B . These results suggest that Glu439 is the preferred methylation site and that Glu446 is potentially a minor methylation site. Gene arrays of the rsbK orthologues and the neighbouring rsbM orthologues are found in a wide range of bacteria. The regulation of sigma factors through metylation of RsbK‐like sensor kinases appears to be widespread in the microbial world.

Is the Evolution of Viviparity Accompanied by a Relative Increase in Maternal Abdomen Size in Lizards? - Yan-Yan Sun; Yu Du; Jing Yang; Tian-Bao Fu; Chi-Xian Lin; Xiang Ji (Evolutionary Biology, 2012)

Ralstonia solanacearum nlpD (RSc1206) contributes to host adaptation - Chi-Yin Hsieh; Jaw-Fen Wang; Pei-Cheng Huang; Der-Kang Lu; Yu-Mei Lin; Wen-Chieh Yang; Chiu-Ping Cheng (European Journal of Plant Pathology, 2012)

A System Dynamic Model and Sensitivity Analysis for Simulating Domestic Pollution Removal in a Free-Water Surface Constructed Wetland - Yung-Chieh Wang; Yu-Pin Lin; Chun-Wei Huang; Li-Chi Chiang; Hone-Jay Chu; Wen-Sheng Ou (Water, Air, & Soil Pollution, 2012)

Relationship between temperature change and the requirement for a permanent pacemaker implantation in bradyarrhythmias - I-Fan Liu; Shih-Lin Chang; Li-Wei Lo; Yu-Feng Hu; Ta-Chuan Tuan; Chi-Woon Kong; Tsu-Juey Wu; Chern-En Chiang; Shih-Ann Chen; Yenn-Jiang Lin (International Journal of Biometeorology, 2011)

Estimation of nested spatial patterns and seasonal variation in the longitudinal distribution of Sicyopterus japonicus in the Datuan Stream, Taiwan by using geostatistical methods - Yu-Pin Lin; Cheng-Long Wang; Chi-Ru Chang; Hsiao-Hsuan Yu (Environmental Monitoring and Assessment, 2011)

Changes of Curdlan Biosynthesis and Nitrogenous Compounds Utilization Characterized in ntrC Mutant of Agrobacterium sp. ATCC 31749 - Li-Jun Yu; Jian-Rong Wu; Zhi-Yong Zheng; Xiao-Bei Zhan; Chi Chung Lin (Current Microbiology, 2011)

A comparative study on arsenic and humic substances in alluvial aquifers of Bengal delta plain (NW Bangladesh), Chianan plain (SW Taiwan) and Lanyang plain (NE Taiwan): implication of arsenic mobilization mechanisms - A. H. M. Selim Reza; Jiin-Shuh Jean; Huai-Jen Yang; Ming-Kuo Lee; Hua-Fen Hsu; Chia-Chuan Liu; Yao-Chang Lee; Jochen Bundschuh; Kao-Hong Lin; Chi-Yu Lee (Environmental Geochemistry and Health, 2011)

Lipopolysaccharide-stimulated activation of murine DC2.4 cells is attenuated by n-butylidenephthalide through suppression of the NF-κB pathway - Ru-Huei Fu; Horng-Jyh Hran; Ching-Liang Chu; Chin-Mao Huang; Shih-Ping Liu; Yu-Chi Wang; Ya-Hsien Lin; Woei-Cherng Shyu; Shinn-Zong Lin (Biotechnology Letters, 2011)

National policy of watershed management and flood mitigation after the 921 Chi-Chi earthquake in Taiwan - Yong-Jun Lin; Yuan-Hsiou Chang; Yih-Chi Tan; Hong-Yuan Lee; Yu-Jia Chiu (Natural Hazards, 2011)

Risk assessment of inhalation exposure to polycyclic aromatic hydrocarbons in Taiwanese workers at night markets - Ping Zhao; Kuo-Pin Yu; Chi-Chi Lin (International Archives of Occupational and Environmental Health, 2011)

Population structure of Nouelia insignis (Asteraceae), an endangered species in southwestern China, based on chloroplast DNA sequences: recent demographic shrinking - Xun Gong; Shan-Shan Luan; Kuo-Hsiang Hung; Chi-Chuan Hwang; Chung-Jean Lin; Yu-Chung Chiang; Tzen-Yuh Chiang (Journal of Plant Research, 2011)

β-Actin is a downstream effector of the PI3K/AKT signaling pathway in myeloma cells - Yen-Peng Ho; Chi-Wei Kuo; Yuan-Tong Hsu; Yu-Shan Huang; Li-Ping Yew; Wei-Feng Huang; Kuo-Chih Lin; Jung-Hsin Hsu (Molecular and Cellular Biochemistry, 2011)

SDF-1α inhibits hypoxia and serum deprivation-induced apoptosis in mesenchymal stem cells through PI3K/Akt and ERK1/2 signaling pathways - Qi Yin; Peifeng Jin; Xuebin Liu; Hua Wei; Xiaoming Lin; Chuang Chi; Yu Liu; Chengchao Sun; Yingjie Wei (Molecular Biology Reports, 2011)

Association between human papillomavirus and adenocarcinoma of rectum and recto-sigmoid junction: a cohort study of 10,612 women in Taiwan - Li-Chung Chuang; Hui-Chi Chen; San-Lin You; Ching-Yu Lin; Mei-Hung Pan; Yi-Chun Chou; Chang-Yao Hsieh; Chien-Jen Chen (Cancer Causes & Control, 2010)

Anti-herpes simplex virus effects of berberine from Coptidis rhizoma, a major component of a Chinese herbal medicine, Ching-Wei-San - Lengsu William Chin; Yu-Wen Cheng; Shih-Shen Lin; Ya-Yun Lai; Long-Yau Lin; Ming-Yung Chou; Ming-Chih Chou; Chi-Chiang Yang (Archives of Virology, 2010)

NYGGF4 homologous gene expression in 3T3-L1 adipocytes: regulation by FFA and adipokines - Ya-ping Zhao; Chun-mei Zhang; Chun Zhu; Xiao-hui Chen; Jia-lin Wang; Chen-bo Ji; Xia Chi; Qin Hong; Yu-zhu Peng; Xi-rong Guo (Molecular Biology Reports, 2010)

Wound repair and anti-oxidative capacity is regulated by ITGB4 in airway epithelial cells - Chi Liu; Hui-jun Liu; Yang Xiang; Yu-rong Tan; Xiao-lin Zhu; Xiao-qun Qin (Molecular and Cellular Biochemistry, 2010)

Roles of cysteines Cys115 and Cys201 in the assembly and thermostability of grouper betanodavirus particles - Chun-Hsiung Wang; Chi-Hsin Hsu; Yi-Min Wu; Yu-Chun Luo; Mei-Hui Tu; Wei-hau Chang; R. Holland Cheng; Chan-Shing Lin (Virus Genes, 2010)

Involvement of the residues of GSKIP, AxinGID, and FRATtide in their binding with GSK3β to unravel a novel C-terminal scaffold-binding region - Shen-Long Howng; Chi-Ching Hwang; Chia-Yi Hsu; Meng-Yu Hsu; Chun-Yen Teng; Chia-Hua Chou; Mei-Feng Lee; Chia-Hung Wu; Shean-Jaw Chiou; Ann-Shung Lieu; Joon-Khim Loh; Chia-Ning Yang; et al. (Molecular and Cellular Biochemistry, 2010)

An integrated approach for identification of polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs) pollutant sources based on human blood contents - Yu-Cheng Chen; Perng-Jy Tsai; Lin-Chi Wang; Minliang Shih; Wen-Jhy Lee (Environmental Science and Pollution Research, 2010)

Empirical Models to Predict Parsimoniously the Mass and Number Concentrations of Ultrafine Particulate in Ambient Atmosphere - Chia-Pin Chio; Man-Ting Cheng; Yu-Chi Lin; Chung-Min Liao (Bulletin of Environmental Contamination and Toxicology, 2009)

Single-Trial Analysis of Cortical Oscillatory Activities During Voluntary Movements Using Empirical Mode Decomposition (EMD)-Based Spatiotemporal Approach - Po-Lei Lee; Li-Zen Shang; Yu-Te Wu; Chih-Hung Shu; Jen-Chuen Hsieh; Yung-Yang Lin; Chi-Hsun Wu; Yu-Lu Liu; Chia-Yen Yang; Chia-Wei Sun; Kuo-Kai Shyu (Annals of Biomedical Engineering, 2009)

Deletion analysis of the C-terminal region of a molecular chaperone DnaK from Bacillus licheniformis - Wan-Chi Liang; Min-Guan Lin; Meng-Chun Chi; Hui-Yu Hu; Huei-Fen Lo; Hui-Ping Chang; Long-Liu Lin (Archives of Microbiology, 2009)

A vitronectin M381T polymorphism increases risk of hemangioblastoma in patients with VHL gene defect - Jing-Shan Huang; Chih-Ming Lin; Yu-Che Cheng; Kun-Long Hung; Chih-Cheng Chien; Shao-Kuan Chen; Chih-Ju Chang; Chan-Wei Chen; Chi-Jung Huang (Journal of Molecular Medicine, 2009)

Characteristics analysis for the flash flood-induced debris flows - Chen Chien-Yuan; Chen Lien-Kuang; Yu Fan-Chieh; Lin Sheng-Chi; Lin Yu-Ching; Lee Chou-Lung; Wang Yu-Ting; Cheung Kei-Wai (Natural Hazards, 2008)

Characteristics of Atmospheric Aerosol and Acidic Gases from Urban and Forest Sites in Central Taiwan - Man-Ting Cheng; Chuen-Liang Horng; Yu-Chi Lin (Bulletin of Environmental Contamination and Toxicology, 2007)

Mitochondrial anchoring of PKCα by PICK1 confers resistance to etoposide-induced apoptosis - Wei-Li Wang; Sheau-Farn Yeh; Eagle Yi-Kung Huang; Yu-Ling Lu; Chun-Fa Wang; Chi-Ying F. Huang; Wey-Jinq Lin (Apoptosis, 2007)

Development of a molecular marker for a bruchid (Callosobruchus chinensis L.) resistance gene in mungbean - Huei-Mei Chen; Chien-An Liu; C. George Kuo; Ching-Mei Chien; Horng-Chi Sun; Chung-Chu Huang; Yu-Chung Lin; Hsin-Mei Ku (Euphytica, 2007)

Replacement of Buried Cysteine from Zebrafish Cu/Zn Superoxide Dismutase and Enhancement of Its Stability via Site-Directed Mutagenesis - Chuian-Fu Ken; Chi-Tsai Lin; Yu-Der Wen; Jen-Leih Wu (Marine Biotechnology, 2007)

A web-based decision support system for slopeland hazard warning - Yu Fan-Chieh; Chen Chien-Yuan; Lin Sheng-Chi; Lin Yu-Ching; Wu Shang-Yu; Cheung Kei-Wai (Environmental Monitoring and Assessment, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Effect of Epstein–Barr virus infection on global gene expression in nasopharyngeal carcinoma - Yuan-Chii Gladys Lee; Yu-Chyi Hwang; Kuang-Chi Chen; Yong-Shiang Lin; Dah-Yeou Huang; Tao-Wei Huang; Cheng-Yan Kao; Han-Chung Wu; Chin-Tarng Lin; Chi-Ying F. Huang (Functional & Integrative Genomics, 2006)

Functional polymorphisms of FGA, encoding α fibrinogen, are associated with susceptibility to venous thromboembolism in a Taiwanese population - Yu-Lin Ko; Lung-An Hsu; Tsu-Shiu Hsu; Chia-Ti Tsai; Ming-Sheng Teng; Semon Wu; Chi-Jen Chang; Ying-Shiung Lee (Human Genetics, 2006)

A GIS Process for Delimitating Areas Potentially Endangered by Debris Flow - Fan-Chieh Yu; Chien-Yuan Chen; Tien-Chien Chen; Feng-Yi Hung; Sheng-Chi Lin (Natural Hazards, 2006)

Directed Mutagenesis of the Conserved Asparagine Residues of Bacillus Stearothermophilus Leucine Aminopeptidase II - Ruey-Shyang Chen; Shin-Ling Yang; Yu-Wen Hua; Meng-Chun Chi; Long-Liu Lin (World Journal of Microbiology and Biotechnology, 2005)

Inhibitory effect of trilinolein on endothelin-1-induced c-fos gene expression in cultured neonatal rat cardiomyocytes - Hung-Yu Yang; Ju-Chi Liu; Yen-Ling Chen; Cheng-Hsien Chen; Heng Lin; Jia-Wei Lin; Wen-Ta Chiu; Jin-Jer Chen; Tzu-Hurng Cheng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2005)

Adsorption-elution purification of chimeric Bacillus stearothermophilus leucine aminopeptidase II with raw-starch-binding activity - Yu-Wen Hua; Meng-Chun Chi; Huei-Fen Lo; Lih-Ying Kuo; Kuo-Lung Ku; Long-Liu Lin (World Journal of Microbiology and Biotechnology, 2005)

The effect of salinity on trichloroethylene co-metabolism by mixed cultures enriched on phenol - Chi-Yuan Lee; Yu-Chia Chan; Chin-Lung Lin (World Journal of Microbiology and Biotechnology, 2005)

Transgenic tomato plants expressing the Arabidopsis NPR1 gene display enhanced resistance to a spectrum of fungal and bacterial diseases - Wan-Chi Lin; Ching-Fang Lu; Jia-Wei Wu; Ming-Lung Cheng; Yu-Mei Lin; Ning-Sun Yang; Lowell Black; Sylvia K. Green; Jaw-Fen Wang; Chiu-Ping Cheng (Transgenic Research, 2004)

Antitermitic and Antifungal Activities of Essential Oil of Calocedrus formosana Leaf and Its Composition - Sen-Sung Cheng; Chi-Lin Wu; Hui-Ting Chang; Yu-Ting Kao; Shang-Tzen Chang (Journal of Chemical Ecology, 2004)

Site-Directed Mutagenesis of the Conserved Threonine, Tryptophan, and Lysine Residues in the Starch-Binding Domain of Bacillus sp. Strain TS-23 a-Amylase - Huei-Fen Lo; Wen-Ying Chiang; Meng-Chun Chi; Hui-Yu Hu; Long-Liu Lin (Current Microbiology, 2004)

A thermostable leucine aminopeptidase from Bacillus kaustophilus CCRC 11223 - Long-Liu Lin; Wen-Hwei Hsu; Cheng-Pu Wu; Meng-Chun Chi; Wei-Mou Chou; Hui-Yu Hu (Extremophiles, 2004)

Identification of essential histidine residues in a recombinant ?-amylase of thermophilic and alkaliphilic Bacillus sp. strain TS-23 - Chen-Tien Chang; Huei-Fen Lo; Meng-Chun Chi; Chia-Yu Yao; Wen-Hwei Hsu; Long-Liu Lin (Extremophiles, 2003)

Geochemical and Sm–Nd isotopic characteristics of metabasites from central Hainan Island, South China and their tectonic significance - Xian‐Hua Li; Hanwen Zhou; Sun‐Lin Chung; Shijiang Ding; Ying Liu; Chi‐Yu Lee; Wenchun Ge; Yeming Zhang; Renjie Zhang (Island Arc, 2002)
Major and trace elements and Sm–Nd isotopic data are presented for metabasites that are present as lenses within Paleozoic metasediments in the Chenxing and Bangxi regions, central Hainan Island, Southeast (SE) China. Most metabasites are metamorphosed cumulated gabbroic rocks tholeiitic in nature, and characterized by varying degrees of depletion in Th, Nb, Ta and light rare earth elements (LREE). Moreover, they show high positive ∈Nd(T) values of approximately +7, similar to those of mid‐ocean ridge basalts (MORB). A Sm–Nd isochron age of 333 ± 12 Ma obtained for the metabasites is interpreted as their crystallization age. The combined geochemical and Sm–Nd isotopic data suggest that the metabasites were generated by dynamic partial melting from a MORB‐like mantle source in an oceanic regime. These rocks probably represent remnants of fragmented oceanic crust of the eastern part of Paleo‐Tethys. They were obducted onto the continental crust as part of the ‘Shilu Mélange’ in earliest Mesozoic time when southern Hainan (part of the Indochina block) collided with northern Hainan (part of South China). Alternatively, they could be formed in a volcanic rifted passive margin at the sea‐floor spreading stage as part of MORB‐like seaward‐dipping reflector break‐up packages.

Calyculin A Sensitive Protein Phosphatase Is Required for Bacillus anthracis Lethal Toxin Induced Cytotoxicity - Jyh-Hwa Kau; Ching-Gong Lin; Hsin-Hsien Huang; Hui-Ling Hsu; Kuo-Ching Chen; Yu-Ping Wu; Hung-Chi Lin (Current Microbiology, 2002)

Identifications, Classification, and Evolution of the Vertebrate α-Amino-3-Hydroxy-5-Methyl-4-Isoxazole Propionic Acid (AMPA) Receptor Subunit Genes - Yu-Chia Chen; Shieh-Shiuh Kung; Bo-Yuan Chen; Chi-Chang Hung; Chun-Chen Chen; Tzi-Yuan Wang; Yi-Mi Wu; Wei-Hsiang Lin; Chyng-Shyan Tzeng; Wei-Yuan Chow (Journal of Molecular Evolution, 2001)